Solid compositions of cannabinoid cocrystals

By using non-crystalline cannabinoid co-crystals or cannabinoid co-crystals with high melting point, the chemical instability and low bioavailability of cannabinoids are solved, and high purity and stable preparation of solid compositions are achieved, suitable for use as a drug .

CN113905730BActive Publication Date: 2025-01-03ENANTIA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201980072674.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-02-01
Filing Date
2019-10-31
Publication Date
2025-01-03
Estimated Expiration
2039-10-31

AI Technical Summary

Technical Problem

The chemical instability and low oral bioavailability of cannabinoids in the prior art lead to difficulties in preparation and use, especially in applications in solid compositions.

Method used

Using non-crystalline cannabinoid co-crystals or cannabinoid co-crystals with high melting points, solid compositions are prepared by simple and cost-effective methods, to enhance the stability of cannabinoids and uniformity of solid compositions, and to form them with water solubility. The combination of substances increases the solubility and bioavailability of cannabinoids.

Benefits of technology

It realizes the high purity preparation of cannabinoids and the preparation of stable solid compositions, meets the standards of medical regulatory agencies, improves the bioavailability and chemical stability of cannabinoids, and is suitable for use as a drug.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003351256460000191
    Figure GDA0003351256460000191
  • Figure GDA0003351256460000201
    Figure GDA0003351256460000201
  • Figure GDA0003351256460000202
    Figure GDA0003351256460000202
Patent Text Reader

Abstract

The present invention relates to solid compositions comprising cannabinoid co-crystals, methods for their preparation and their use in therapy or cannabinoid purification. It also relates to co-crystals of cannabinoids.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims the benefit of European Patent Application No. 18382776.5 filed on October 31, 2018 and European Patent Application No. 19382074.3 filed on February 1, 2019.

[0002] The present invention relates to solid compositions comprising cannabinoid co-crystals, methods for their preparation, and their use in therapy and cannabinoid purification. It also relates to co-crystals of cannabinoids. Background Art

[0003] The cannabis plant (Cannabis sativa plant) has been used medicinally for hundreds of years. It contains three main classes of bioactive molecules: flavonoids, terpenes, and more than 60 cannabinoids, including cannabidiol (abbreviated as (-)-CBD or CBD), trans-(-)-Δ 9 -Tetrahydrocannabinol (abbreviated as Δ 9 -THC, (-)-Δ 9 -THC, trans-(-)-(-)-Δ 9 Cannabis sativa L. is a cannabinoid found in cannabis plants. It is a cannabinoid found in cannabis plants in the form of cannabinoids ...

[0004] In addition, other semi-synthetic cannabinoids are being developed to optimize their properties. Some examples include HU-580 (a derivative of CBDA - British Journal of Pharmacology, 2018, 175 100–112) and VCE-003.2 (a derivative of CBG - Sci Rep, 2016, 6:29789, 1-15). This undoubtedly expands the number of cannabinoid possibilities.

[0005] Cannabinoids are a complex family of terpene phenolic compounds that exert most of their effects by binding to and activating specific Gαi protein-coupled receptors called cannabinoid receptors, such as CB1 and CB2. Several strains of cannabis plants have been found to have significant variation in the ratios of each cannabinoid, and also contain some cannabinoids (such as THC) that have psychoactive effects mediated by CB1 receptors located in the central nervous system.

[0006] The use of cannabinoids in treatment is questionable due to psychotropic and addictive issues. Despite the psychotropic effects of some cannabinoids, cannabinoid receptors and their endogenous ligands are used as putative molecular targets for the treatment of various diseases including neurodegenerative diseases (Alzheimer's disease, Parkinson's disease, Huntington's disease, etc.), neuropathic and inflammatory pain, glaucoma, multiple sclerosis, cardiovascular disease, and obesity. In addition, the role of cannabinoids in the field of cancer research through their ability to target tumors has also been explored. In fact, several preclinical studies suggest that THC has in vitro anticancer effects on lung cancer, glioma, thyroid epithelial tumors, lymphomas, skin cancer, uterine cancer, breast cancer, prostate cancer, pancreatic cancer, and neuroblastoma. Finally, cannabinoids also have palliative effects by suppressing nausea and vomiting associated with chemotherapy or radiotherapy in cancer patients; stimulating appetite; relieving pain; improving mood and relieving insomnia. Minor cannabinoids have shown promise as non-opioid analgesics, but these substances have been rarely studied to understand their effects (especially on a chronic basis) and potential mechanisms because they are difficult to isolate in sufficient quantities to conduct these studies.

[0007] The use of cannabinoids in therapy means preparing appropriate compositions that meet the stringent standards of regulatory agencies. However, the chemical and physical properties of cannabinoids hinder the preparation of oral compositions containing them without compromising the desired chemical stability of the cannabinoids and with adequate oral bioavailability.

[0008] Cannabinoids are generally sensitive to the conditions usually used for their preparation and storage. It is known that some cannabinoids may be oxidized or decomposed into undesirable byproducts in alkaline or acidic media and / or in the presence of air and / or when exposed to light. In particular, it is disclosed in the prior art that in alkaline media and in the presence of air, CBD is oxidized; while under acidic conditions, CBD is cyclized to give the undesirable byproduct THC, which causes psychoactive effects. Tetrahydrocannabinol can also undergo oxidation to become CBN, which is used as a chemical indicator of poor or excessive storage conditions of cannabis plants.

[0009] Additionally, some cannabinoids, such as CBD, are also known to be photoreactive, which means they should be protected from light when stored.

[0010] In order to overcome the low chemical stability during cannabinoid preparation, multiple synthetic routes have been developed to prepare cannabinoids, particularly CBD, THC, CBN, CBG and CBDV.

[0011] In the case of CBD, it can be obtained from plants such as the cannabis genus by several methods, either by synthetic routes or by extraction methods. On the one hand, the extraction methods of CBD generally involve one or more steps of extraction from the cannabis plant; followed by a decarboxylation step to convert the cannabinoids in acid form (e.g. tetrahydrocannabinolic acid (THCA) and cannabidiolic acid (CBDA)) into neutral cannabinoids in the form of a mixture (including THC and CBD); and supplying the mixture thus obtained to one or more purification steps. On the other hand, several synthetic methods for the preparation of CBD are also disclosed in the prior art. In particular, these synthetic methods are based on the acid-catalyzed terpenization of phenols (e.g., the acid-catalyzed condensation of (+)-p-menth-2,8-dien-1-ol with olivetol). The reaction conditions of these reactions involve the use of N,N-dimethylformamide dineopentyl acetal (see T.Petrzilka et al. "synthese und des(-)-cannabidiols mitteilung". Helvetica Chimica Acta. 1967, 50 (2) volume, 719-23 pages); picric acid, oxalic acid or maleic acid (see T. Petrzilka et al. "synthese von haschisch-inhaltsstoffen. 4. Mitteilung". Helvetica Chimica Acta. 1969, 52 (4) volume, 1102-34 pages); p-toluenesulfonic acid (PTSA) (see PCT patent application WO2009018389); or BF3-Et2O / alumina (see Tetrahedron Letters 1985, 26 (8), 1083); or ZnCl2 (see PCT patent application WO2006133941).

[0012] In the case of THC, it can also be obtained from natural products (such as hashish or marijuana) either through synthetic routes or through extraction methods. Some of these methods involve extracting the derivative from the flowers of the cannabis plant. 9 -Tetrahydrocannabinolic acid (also known as Δ 9 -THC acid or THCA), which is subsequently converted to THCA salt, which is then extracted and converted back to Δ 9 -THC carboxylic acid. Finally, by solvent exchange, Δ 9 -THC carboxylic acid is decarboxylated and extracted again with an organic solvent and then purified to obtain Δ 9-THC. Another known synthesis method is based on the reaction of (+)-p-menth-2,8-diene-1-ol with a cis / trans mixture of olive phenol in the presence of an acid catalyst such as p-toluenesulfonic acid and a dehydrating agent; or cannabidiol in ethanol in the presence of hydrochloric acid (J.Am.Chem.Soc.1964, Vol. 86, p. 1646) or in an inert solvent under anhydrous conditions with a Lewis acid such as BF3-Et2O (J.Am.Chem.Soc., 1971, Vol. 93, p. 217-224). (Mechoulam R. and Ben-Zvi Z., Chem Commun, 1969, 7, 343-344) Its synthesis from CBD was subsequently reported.

[0013] In the case of minor cannabinoids, since their proportion in natural cannabis extracts is very low, they can also be obtained by synthetic routes to overcome the separation problem. In addition, synthetic preparations allow the preparation of sufficient quantities for in vivo studies and clinical trial studies, but it is difficult to achieve the required high purity without column chromatography. In the case of CBDV, it can be obtained by a similar synthesis to CBD, but the starting material derived from olive phenol is not commercially available and must be prepared in two steps from 1-bromo-3,5-dimethoxybenzene according to the method described in Tetrahedron 2017, 73, 5297-5301). In the case of CBN, it can be prepared directly from CBD by reaction with iodine in toluene at 110°C (J.Nat.Prod.2018, 81(3), 630-633). In the case of CBG, it can be obtained following a one-step synthetic route starting from commercially available geraniol and olivetol using the catalyst p-toluenesulfonic acid (PTSA) or Lewis acid (Tet. Lett. 1985, 26(8), 1083-1086).

[0014] However, these methods produce the target cannabinoid with considerable numbers of undesirable by-products (including, in some cases, related compounds that are difficult to separate by crystallization or column chromatography).

[0015] The purification steps of the preparation or extraction methods disclosed above may include evaporation steps (to remove volatile impurities); winterization procedures (to remove wax impurities); filtration through a plug of silica gel (to remove highly polar impurities); column chromatography, crystallization and high vacuum (to remove residual solvent); or the use of a combination of fractional distillation and crystallization of the cannabinoid from an organic solvent medium. All of these purification steps are laborious, time-consuming, uneconomical, and even if they are used, the cannabinoid may still be obtained in low yield.

[0016] Therefore, methods for increasing the purity of cannabinoids have been disclosed in the prior art. In particular, in the case of CBD, it is known that the use of esters of olivetol phenolic acid instead of olivetol as starting material results in an increase in the purity of CBD (see PCT patent applications WO2007041167 and WO2015032519). In these methods, at least an additional decarboxylation step is required to obtain pure CBD. However, esters of olivetol phenolic acid are very expensive and their use hinders the cost effectiveness of this approach. As disclosed above for CBD, several purification methods have also been disclosed in the art with the aim of increasing Δ 9 -THC purity. Some of these methods involve fractional distillation under vacuum to separate volatile cannabinoids from low-boiling and non-volatile components; using Sephadex LH20 TM Column (see Biochemical Medicine, 1973, 8 (3), 341-344; and WO2004026857A2-GWPharma); accelerated microgel chromatography (see Preparative Biochemistry, 1973, 3 (3), 209-220); or orthogonal chromatography using normal phase and reverse phase flash chromatography (see poster ACS, Philadelphia, 2016, Biotage), chromatographic separation. In order to improve the separation of Δ 9 -THC was separated from various impurities to prepare Δ 9 -THC derivatives (Δ 9 -THC ester). Due to (-)-Δ 9 -THC does not crystallize. WO2006053766A1 discloses the use of racemic (±)-Δ 9 -THC or (±)-Δ 9 -THC m-nitrobenzenesulfonate crystallization followed by separation of the two enantiomers by chiral chromatography to purify the crude product. However, the synthesis of (+)-Δ 9 -THC can be prepared (±)-Δ 9 -THC, since the racemic form is not a natural compound. Another purification method is also disclosed, comprising heating Δ 9 -Tetrahydrocannabinolic acid ((-)-THCA) crystallizes as a light yellow crystalline solid with a melting point in the range of 45-48°C (see US2017008870A1). Finally, the prior art also discloses Δ 9 The method comprises separating the ester formed from the crude mixture by chromatography, followed by first hydrolyzing the ester and then separating the resulting Δ 9 -THC distillation under reduced pressure. (See US4381399A).

[0017] Unfortunately, fractionation of cannabinoids is usually not effective in separating isomers or other related cannabinoids from each other. In addition, since some cannabinoids, such as THC, are heat sensitive, this purification technique may also result in degradation products. Furthermore, purification by chromatography is expensive and difficult to carry out on an industrial scale. In order to meet the purity requirements, in some cases, it may be necessary to perform several chromatographic purifications using different columns and non-friendly solvents.

[0018] On the other hand, some of these cannabinoids described as oily or gummy products (e.g., CBC, THC, or Δ8-THC) are difficult to handle and are generally less chemically stable than in crystalline form.

[0019] In the case of THC, it has been disclosed as a resinous, pale yellow oil and a semi-solid product, even when obtained in very high purity. Unfortunately, this physical state hinders its manufacture and purification and is not easily adaptable to incorporation into standard dosage forms commonly available for other solid pharmaceutical compounds.

[0020] While obtaining and purifying cannabinoids is complex, formulating these products into solid compositions such as tablets, hard gelatin capsules and granules is even more complex and has certainly not yet been effectively addressed.

[0021] An important disadvantage of some cannabinoids (such as CBD, CBG and CBN) with respect to their formulation is their low melting point (about 52-77°C), resulting in potential local melting processes during high-energy formulation steps such as grinding, pressing and coating processes; or resulting in oily / pasty amorphous products (such as THC and Δ8-THC). In both cases, there may be a significant risk of chemical stability of the cannabinoids during the formulation of these formulations and during storage. This property also jeopardizes the stability and homogeneity of the solid formulation itself, regardless of the stability of the active ingredient itself. Therefore, it is not recommended to prepare solid formulations of cannabinoids.

[0022] All of the above-mentioned drawbacks with respect to the preparation of suitable oral compositions disclosed above have led to the development of oral liquid compositions, such as those already approved in different regulatory agencies. In fact, despite the great advantages of solid compositions, the approved oral compositions containing cannabinoids are still in the form of solutions or emulsions.

[0023] In particular, Sativex is an oromucosal spray containing extracts obtained from the cannabis plant, including tetrahydrocannabinol (THC) and cannabidiol (CBD). Sativex has been approved in several countries to treat conditions including cancer pain and ankylosing pain from multiple sclerosis. On the other hand, THC is also approved as Marinol, which is supplied in round soft gelatin capsules (for oral use) that contain THC dissolved in sesame oil. Marinol is indicated for the treatment of anorexia associated with weight loss in patients with acquired immune deficiency syndrome (AIDS), and is also indicated for the treatment of nausea and vomiting associated with cancer chemotherapy in adults.

[0024] Recently, the US Food and Drug Administration (FDA) approved Epidiolex, the first prescription drug made from the cannabis plant that contains highly purified cannabidiol (CBD). This is advantageous because it does not cause the addictive effects (also known as the 'high') associated with the presence of THC. Epidiolex is marketed as an oral solution containing CBD to treat seizures associated with two rare and severe forms of epilepsy - Lennox-Gastaut syndrome and Dravet syndrome in children.

[0025] However, these orally administrable liquid preparations still have some disadvantages. First, the excipients they contain cause lesions, ulcers, pain and soreness of the oral mucosa, resulting in interruptions in treatment. Second, they also contain ethanol as a medium and are not recommended for people who suffer from or have suffered from alcohol addiction. Third, the stability of the cannabinoids dissolved in the liquid composition is compromised, resulting in an increased degradation rate of the cannabinoids, shortening the shelf life of such preparations. Fourth, these liquid compositions are oral mucosal absorption compositions with significant inter-subject variability in their pharmacokinetic profiles, resulting in an increase in the number of daily dose administrations to ensure pharmacological activity.

[0026] Furthermore, another major drawback of cannabinoids is their low oral bioavailability (ranging from 6-33% in humans). This low bioavailability is due to its low water solubility combined with extensive first-pass metabolism.

[0027] In order to overcome its very low water solubility and obtain a solid composition, complexes with cyclodextrins or maltodextrins suitable for sublingual administration have been disclosed in the prior art. These complexes are obtained by evaporation to dryness or by coprecipitation followed by freeze drying, which means that these complexes are not in crystalline form, which hinders the preparation of pharmaceutical compositions containing them. In addition, these complexes may reduce the bioavailability of the active ingredient.

[0028] Other alternative preparations that overcome its low oral bioavailability are to prepare oral preparations in contact with aqueous media, producing cannabinoid nanoparticles with a size less than 500nm. This is achieved by using a liquid preparation comprising a surfactant, a lipid component and a water-soluble amphiphilic solvent. These liquid compositions can be converted into solid-loaded compositions by adsorbing them onto a solid substrate using poly (meth) acrylate as a stratifying agent or coating agent. Unfortunately, the preparation of these solid-loaded compositions means a complicated process, first meaning the preparation of a pre-concentrated emulsion of cannabinoids, which is then deposited in a solid support (see US2018325861). As described above, even in liquid form and during the preparation of solid-loaded solid preparations, excessive manipulation of cannabinoids also hinders the chemical stability of cannabinoids and their oral bioavailability. In addition, the appropriate and effective release of cannabinoids from a solid support may also be impaired.

[0029] Thus, as is known from the prior art, there has long been a need to find a solid composition for oral administration comprising one or more cannabinoids which meets strict regulatory requirements and has adequate oral bioavailability. Summary of the invention

[0030] The inventors have provided a solid composition suitable for oral administration which overcomes the problems disclosed in the prior art relating to the chemical instability of cannabinoids during their preparation and during the manufacture and storage of compositions containing them; as well as the side effects associated with their oral administration and low bioavailability. The solid composition also overcomes the problems associated with cannabinoid solid compositions themselves.

[0031] In particular, the inventors have found that the use of co-crystals of non-crystalline cannabinoids or co-crystals of cannabinoids having a higher melting point than the cannabinoids allows the preparation of solid compositions by a simple, cost-effective and industrially scalable process without compromising the stability of the cannabinoids in the composition or the stability of the solid composition itself and the homogeneity of the solid composition. In fact, the increase in the melting point allows the reduction of potential amorphization due to local melting of the cannabinoids during the preparation of the oral composition and even during its storage. Therefore, the higher stability of the co-crystals of cannabinoids makes them suitable for use as a medicament, since the solid composition of the invention containing said co-crystals meets the standards of the strict impurity limit specifications of medical regulatory agencies.

[0032] In addition, the inventors have unexpectedly discovered that the physical and mechanical properties of cannabinoid co-crystals are suitable for the preparation of solid compositions. As shown in the examples of the present invention, the use of cannabinoid co-crystals allows the preparation of simple solid compositions with few ingredients and with a high content of active ingredients (1 to 80% by weight) and easy commercial utilization; which can be prepared by simple methods. In particular, both direct compression and dry granulation by pre-compression can be used to prepare tablets containing the composition.

[0033] Furthermore, the inventors have found that the solid compositions of the present invention comprising one or more cannabinoid co-crystals (having a high melting point) allow for adequate bioavailability even for use as a medicament. Without being bound by any theory, it appears that the co-crystals enhance the solubility of poorly water-soluble cannabinoids without changing their molecular structure. In particular, the crystalline phase containing the cannabinoid and the coformer dissociates in a short period of time in the biological medium. The coformer (which is the more water-soluble component in the co-crystal) is extracted from the crystal lattice into the aqueous medium. After dissociation, the hydrophobic cannabinoid becomes supersaturated in the aqueous biological medium, and this higher energy form is maintained for a sufficiently long period of time, thereby allowing it to be absorbed before precipitation.

[0034] Another part of the present invention is that the use of cannabinoid co-crystals allows the preparation of cannabinoids of high purity and their maintenance during the process of manufacturing the solid composition. In fact, the use of cannabinoid co-crystals allows a simple, cost-effective and industrially scalable method to purify cannabinoids such as CBD, THC, CVDV and CBN, even when the cannabinoids are obtained by plant extraction processes or synthetic routes. Therefore, the solid composition of the present invention containing cannabinoid co-crystals complies with the impurity profile required by regulatory agencies.

[0035] Thus, the inventors have discovered that the use of cannabinoid co-crystals provides a completely unexpected dual functionality, allowing the purification of cannabinoids and the simultaneous preparation of solid compositions containing them.

[0036] Therefore, the use of cannabinoid co-crystals to prepare stable solid compositions containing them is considered a contribution to the art.

[0037] Thus, a first aspect of the present invention is directed to a solid composition comprising an effective amount of co-crystals of one or more cannabinoids and zwitterionic coformers; and one or more acceptable excipients or carriers; wherein the effective amount of the co-crystals is from 1 to 80% by weight of the solid composition.

[0038] A second aspect of the present invention relates to co-crystals of a cannabinoid selected from CBD, THC and Δ8-THC and a zwitterionic coformer.

[0039] A third aspect of the invention relates to a process for the preparation of a co-crystal as defined in the second aspect of the invention, said process comprising: (c) slurrying a cannabinoid with a coformer and an organic solvent; and (d) isolating the co-crystals thereby obtained.

[0040] Finally, a fourth aspect of the present invention relates to a method for purifying a cannabinoid, the method comprising: (e) dissociating the co-crystal as defined herein under such reaction conditions to obtain a cannabinoid; and (f) isolating the cannabinoid thus obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Shown is an X-ray diffraction pattern (XRPD) of co-crystal Form I. The spectrum represents intensity (I; counts) versus degrees 2θ (°).

[0042] Figure 2 Shown is the TGA of co-crystal Form I. The thermogram represents weight loss (% w / w) versus temperature (°C).

[0043] Figure 3 An X-ray diffraction pattern (XRPD) of co-crystal Form II is shown. The spectrum represents intensity (I; counts) versus 2θ degrees (°).

[0044] Figure 4 Shown is an X-ray diffraction pattern (XRPD) of co-crystalline Form III. The spectrum represents intensity (I; counts) versus 2θ degrees (°).

[0045] Figure 5 Shown are the 1H NMR spectra of the cannabis flower extract containing 50% w / w CBD (sample A) used as starting material in Example B.2 and the 1H NMR spectrum of CBD recovered after dissociation of co-crystal Form I obtained in Example B.2 (spectrum B).

[0046] Figure 6 Shown are the X-ray diffraction patterns (XRPD) of commercially available pure CBD (Diffractogram B) and of CBD isolated from co-crystal Form I obtained in Example B.2 (Diffractogram A). The spectra represent intensity (I; counts) versus 2θ degrees (°).

[0047] Figure 7 Shown is an X-ray diffraction pattern (XRPD) of co-crystal Form IV. The spectrum represents intensity (I; counts) versus degrees 2θ (°).

[0048] Figure 8 Shown is the DSC of co-crystal Form IV. The spectrum represents heat flow (mW / mg) versus temperature (°C).

[0049] Fig. 9Shown is an X-ray diffraction pattern (XRPD) of co-crystalline Form V. The spectrum represents intensity (I; counts) versus degrees 2θ (°).

[0050] Fig.10 Shown is the DSC of co-crystal Form V. The spectrum represents heat flow (mW / mg) versus temperature (°C).

[0051] Fig.11 Shown is the DSC of co-crystal Form I. The spectrum represents heat flow (mW / mg) versus temperature (°C).

[0052] Fig.12 Shown is an X-ray diffraction pattern (XRPD) of co-crystalline Form VI. The spectrum represents intensity (I; counts) versus 2θ degrees (°).

[0053] Fig.13 Shown is the DSC of co-crystal Form VI. The spectrum represents heat flow (mW / mg) versus temperature (°C).

[0054] Fig.14 An X-ray diffraction pattern (XRPD) of co-crystalline Form VII is shown. The spectrum represents intensity (I; counts) versus 2θ degrees (°).

[0055] Fig.15 The DSC of co-crystal Form VII is shown. The spectrum represents heat flow (mW / mg) versus temperature (°C).

[0056] Fig.16 An X-ray diffraction pattern (XRPD) of co-crystalline Form VIII is shown. The spectrum represents intensity (I; counts) versus 2θ degrees (°).

[0057] Fig.17 Shown is the DSC of co-crystal Form VIII. The spectrum represents heat flow (mW / mg) versus temperature (°C).

[0058] Fig.18 An X-ray diffraction pattern (XRPD) of co-crystal Form IX is shown. The spectrum represents intensity (I; counts) versus 2θ degrees (°).

[0059] Fig.19 Shown is an X-ray diffraction pattern (XRPD) of co-crystal Form X. The spectrum represents intensity (I; counts) versus degrees 2θ (°).

[0060] Fig. 20 An X-ray diffraction pattern (XRPD) of co-crystalline Form XI is shown. The spectrum represents intensity (I; counts) versus 2θ degrees (°).

[0061] Fig.21The DSC of co-crystal Form XI is shown. The spectrum represents heat flow (mW / mg) versus temperature (°C).

[0062] Fig. 22 Shown is an X-ray diffraction pattern (XRPD) of co-crystalline Form XII. The spectrum represents intensity (I; counts) versus 2θ degrees (°).

[0063] Fig.23 Shown is the DSC of co-crystal Form XII. The spectrum represents heat flow (mW / mg) versus temperature (°C).

[0064] Fig.24 An X-ray diffraction pattern (XRPD) of co-crystalline Form XIII is shown. The spectrum represents intensity (I; counts) versus 2θ degrees (°).

[0065] Fig.25 Shown is the DSC of co-crystal Form XIII. The spectrum represents heat flow (mW / mg) versus temperature (°C).

[0066] Fig.26 Shown is an X-ray diffraction pattern (XRPD) of co-crystalline Form XIV. The spectrum represents intensity (I; counts) versus 2θ degrees (°).

[0067] Fig. 27 Shown is the DSC of co-crystal Form XIV. The spectrum represents heat flow (mW / mg) versus temperature (°C).

[0068] Fig.28 Shown is an X-ray diffraction pattern (XRPD) of co-crystal Form XV. The spectrum represents intensity (I; counts) versus 2θ degrees (°).

[0069] Fig.29 Shown is the DSC of co-crystal Form XV. The spectrum represents heat flow (mW / mg) versus temperature (°C).

[0070] Fig.30 Shown is an X-ray diffraction pattern (XRPD) of co-crystalline Form XVI. The spectrum represents intensity (I; counts) versus 2θ degrees (°).

[0071] Fig.31 Shown is the DSC of co-crystal Form XVI. The spectrum represents heat flow (mW / mg) versus temperature (°C).

[0072] Fig.32 Shown is an X-ray diffraction pattern (XRPD) of co-crystalline Form XVII. The spectrum represents intensity (I; counts) versus 2θ degrees (°).

[0073] Fig.33Shown is the DSC of co-crystal Form XVII. The spectrum represents heat flow (mW / mg) versus temperature (°C).

[0074] Fig.34 An X-ray diffraction pattern (XRPD) of co-crystalline Form XVIII is shown. The spectrum represents intensity (I; counts) versus 2θ degrees (°).

[0075] Fig.35 The DSC of co-crystal Form XVIII is shown. The spectrum represents heat flow (mW / mg) versus temperature (°C).

[0076] Fig.36 Shown is an X-ray diffraction pattern (XRPD) of co-crystalline Form XIX. The spectrum represents intensity (I; counts) versus 2θ degrees (°).

[0077] Fig.37 Shown is the DSC of co-crystal Form XIX. The spectrum represents heat flow (mW / mg) versus temperature (°C). DETAILED DESCRIPTION

[0078] Unless otherwise stated, all terms used herein in this application should be understood with their ordinary meanings known in the art. Other more specific definitions of certain terms used in this application are described below and are intended to be uniformly applied throughout the specification and claims, unless otherwise explicitly stated definitions provide a broader definition.

[0079] For the present invention, any range given includes the lower and upper endpoints of the range. Unless otherwise specified, given ranges and values, such as temperature, time, etc., should be regarded as approximate values.

[0080] When values ​​of characteristic peaks of an X-ray diffraction pattern are given, it can be said that these are "approximate" values. It should be understood that the values ​​stated are ±0.3 of the values ​​shown in the corresponding list or table in an X-ray diffractometer using Cu-Kα radiation. Measured in 2θ degrees.

[0081] The term "weight percent (%)" refers to the percentage of each component relative to the total weight of the composition.

[0082] Thus, a first aspect of the present invention is directed to a solid composition comprising an effective amount of co-crystals of one or more cannabinoids and zwitterionic coformers; and one or more acceptable excipients or carriers; wherein the effective amount of the co-crystals is from 1 to 80% by weight of the solid composition.

[0083] In one embodiment, the solid composition of the present invention comprises an effective amount of the co-crystal, the effective amount being 4 to 70% by weight of the solid composition; particularly 6% to 60%, more particularly 9% to 40%.

[0084] For the purposes of the present invention, the term "solid composition" refers to any solid composition in the absence of a liquid medium. The solid composition of the present invention can be prepared according to methods known in the prior art. Suitable excipients and / or carriers and their amounts can be easily determined by those skilled in the art according to the type of preparation being prepared.

[0085] In one embodiment, the solid composition is a "pharmaceutically acceptable solid composition" comprising a "pharmaceutically effective amount of a co-crystal" and one or more "pharmaceutically acceptable excipients or carriers", wherein the co-crystal comprises a cannabinoid and a "pharmaceutically acceptable coformer". The term "pharmaceutically acceptable solid composition" refers to a solid composition suitable for use in pharmaceutical technology for medical purposes. The term "pharmaceutically effective amount of a co-crystal" refers to the amount of the co-crystal provided after dissociation of the co-crystal following administration of a therapeutically (pharmaceutically) effective amount of a cannabinoid. The term "pharmaceutically acceptable coformer" refers to a coformer suitable for use in the preparation of a pharmaceutical composition for medical purposes. It must also be suitable for use in contact with tissues or organs of humans and animals without excessive toxicity, irritation, allergic reaction, immunogenicity, or other problems or complications commensurate with a reasonable benefit / risk ratio. The term "pharmaceutically acceptable excipient or carrier" refers to an excipient or carrier suitable for use in pharmaceutical technology for the preparation of a composition for medical purposes. Each component must be acceptable in the sense of being compatible with the other ingredients of the composition. It must also be suitable for use in contact with human and animal tissues or organs without excessive toxicity, irritation, allergic response, immunogenicity, or other problems or complications commensurate with a reasonable benefit / risk ratio.

[0086] In one embodiment, the pharmaceutical solid composition of the present invention can be formulated into any form including any single unit dosage form and any multiple unit dosage form. The term "single unit" includes one entity, such as a single tablet, a single capsule, a single granule, a powder, and a single pill. The term "single unit dosage form" defines a dosage form consisting of only one unit, which unit contains an effective amount of cannabinoid co-crystals. The term "multiple unit dosage form" defines a dosage consisting of more than one unit containing an effective amount of cannabinoid co-crystals. Typically, multiple unit dosage forms are based on subunits such as granules, pellets or mini-tablets. They are usually delivered in hard capsules or converted to tablets. Therefore, unit dosage forms comprising the composition of the present invention are also part of the present invention. In one embodiment, the unit dosage form comprising the composition of the present invention is a single unit dosage form. In one embodiment, the unit dosage form comprising the composition of the present invention is a multiple unit dosage form. In one embodiment, the solid composition is a capsule; in particular a hard capsule. In one embodiment, the solid composition is a tablet; in particular a directly compressed tablet or a dry granulated tablet.

[0087] In one embodiment, the pharmaceutical solid composition is an immediate release composition. In one embodiment, the pharmaceutical solid composition is a modified release composition. The term "modified release" refers to a composition that changes the rate at which cannabinoids are released from the composition after administration, depending on the specific circumstances surrounding the case and the specific condition being treated. In other words, it is a composition that exhibits a different cannabinoid release compared to a conventional immediate release composition administered by the same route. For purposes of the present invention, the term "modified release" includes controlled release, sustained release, prolonged release, or extended release.

[0088] Pharmaceutical compositions as defined above comprise suitable excipients or carriers, including but not limited to binding agents, fillers, disintegrants, glidants, lubricants or mixtures thereof. In addition, compositions of the present invention may contain other ingredients, for example coloring agents, and other components known in the prior art used in pharmaceutical compositions.

[0089] The term "binder" refers to any pharmaceutically acceptable compound with a binding property. Materials commonly used as binders include: povidones such as polyvinyl pyrrolidone, methylcellulose polymers, hydroxyethyl cellulose, hydroxypropyl cellulose, L-hydroxypropyl cellulose (low-substituted), hydroxypropyl methylcellulose (HPMC), sodium carboxymethyl cellulose, carboxymethylene, carboxymethyl hydroxyethyl cellulose and other cellulose derivatives, starch or modified starch, gelatin, sugars such as sucrose, glucose and sorbitol, gums such as gum arabic, tragacanth, agar and carrageenan; and mixtures thereof. In one embodiment, the composition of the present invention is a composition in which a pharmaceutically acceptable excipient or carrier comprises one or more binders, preferably a composition comprising polyvinyl pyrrolidone. In one embodiment, the composition of the present invention is a composition in which a pharmaceutically acceptable excipient or carrier comprises one or more binders, and the amount of the binder is 1 to 10% by weight of the composition, preferably 1 to 6% by weight, and more preferably 1 to 3% by weight.

[0090] The terms "filler" and "diluent" have the same meaning and are used interchangeably. They refer to any pharmaceutically acceptable excipient or carrier (material) that fills the size of the composition, making it practical for manufacture and convenient for consumers to use. The materials commonly used as fillers include calcium carbonate, calcium phosphate, calcium hydrogen phosphate, tribasic calcium sulfate, carboxymethylcellulose calcium, cellulose, cellulose products such as microcrystalline cellulose and its salts, dextrin derivatives, dextrin, glucose, fructose, lactitol, lactose, starch or modified starch, magnesium carbonate, magnesium oxide, maltitol, maltodextrin, maltose, mannitol, sorbitol, starch, sucrose, sugar, xylitol, erythritol and mixtures thereof. In one embodiment, the composition of the present invention is a composition in which a pharmaceutically acceptable excipient or carrier comprises one or more fillers, preferably microcrystalline cellulose and its salts.

[0091] The term "disintegrant" refers to a substance that helps the composition break up once ingested. Materials commonly used as disintegrants are, but are not limited to, cross-linked polyvinyl pyrrolidone; starches such as corn starch and dried sodium starch glycolate; gums such as corn starch and dried sodium starch glycolate; gums such as alginic acid, sodium alginate, guar gum; cross-linked sodium carboxymethyl cellulose; low-substituted hydroxypropyl cellulose and mixtures thereof. In one embodiment, the composition of the present invention is a composition in which the pharmaceutically acceptable excipient or carrier comprises one or more disintegrants, preferably cross-linked sodium carboxymethyl cellulose.

[0092] The term "glidant" refers to a substance that improves the flow characteristics of a powder mixture in a dry state. Materials commonly used as glidants include magnesium stearate, colloidal silicon dioxide or talc. In one embodiment, the composition of the present invention is a composition in which a pharmaceutically acceptable excipient or carrier comprises one or more glidants, preferably magnesium stearate, talc or a mixture thereof.

[0093] The term "lubricant" refers to a material that prevents the composition ingredients from caking together and prevents sticking on a tablet punch or capsule filling machine and improves the fluidity of the composition mixture. The material commonly used as a lubricant includes sodium oleate, sodium stearate, sodium benzoate, sodium stearate, sodium chloride, stearic acid, sodium stearyl fumarate, calcium stearate, magnesium stearate, magnesium lauryl sulfate, sodium stearyl fumarate, sucrose esters or fatty acids, zinc, polyethylene glycol, talcum powder and mixtures thereof. When the composition is a tablet, in order to improve the tableting process, the presence of a lubricant is particularly preferred. In one embodiment, the composition of the present invention is a composition in which a pharmaceutically acceptable excipient or carrier comprises one or more lubricants, preferably comprises magnesium stearate.

[0094] The pharmaceutical composition of the present invention can be prepared according to methods known in the prior art. Suitable excipients and / or carriers and their amounts can be easily determined by those skilled in the art according to the type of preparation to be prepared.

[0095] In one embodiment, the pharmaceutical composition is a tablet. In one embodiment, the pharmaceutical composition is a direct compression tablet.

[0096] In one embodiment, the pharmaceutically acceptable direct compression tablet comprises:

[0097] 1 to 80% by weight of one or more cannabinoid co-crystals;

[0098] 20 to 99 weight percent of one or more fillers; and

[0099] 0.25 to 10% by weight of one or more glidants;

[0100] The sum of the components of the composition is 100% by weight.

[0101] In one embodiment, the pharmaceutically acceptable direct compression tablet comprises:

[0102] 9 to 40% by weight of one or more cannabinoid co-crystals;

[0103] 50 to 90% by weight microcrystalline cellulose; and

[0104] 0.25 to 2% by weight of magnesium stearate;

[0105] The sum of the components of the composition is 100% by weight.

[0106] The process for preparing direct compression tablets involves only blending the ingredients in the proper order without granulation and avoids the use of organic solvents, water and / or high temperatures in which the cannabinoids may degrade.

[0107] In one embodiment, the pharmaceutical composition is a dry granulated tablet.

[0108] In one embodiment, the pharmaceutical dry granulation tablet comprises:

[0109] 1 to 80% by weight of one or more cannabinoid co-crystals;

[0110] 20 to 99 weight percent of one or more fillers;

[0111] 1 to 15% by weight of one or more disintegrants;

[0112] 0.25 to 10% by weight of one or more glidants; and

[0113] 0.25 to 10 wt. % of one or more lubricants;

[0114] The sum of the components of the composition is 100% by weight.

[0115] In one embodiment, the pharmaceutical dry granulation tablet comprises:

[0116] 9 to 40% by weight of one or more cannabinoid co-crystals;

[0117] 50 to 90% by weight of one or more fillers;

[0118] 1 to 6% by weight of one or more disintegrants;

[0119] 0.25 to 4% by weight of one or more glidants; and

[0120] 0.25 to 2 wt. % of one or more lubricants;

[0121] The sum of the components of the composition is 100% by weight.

[0122] In one embodiment, the pharmaceutical dry granulation tablet comprises:

[0123] 30 to 40% by weight of one or more cannabinoid co-crystals;

[0124] 50 to 60% by weight microcrystalline cellulose;

[0125] 2 to 4 weight percent croscarmellose sodium;

[0126] 0.5 to 2% by weight of magnesium stearate; and

[0127] 1 to 4% by weight of talc;

[0128] The sum of the components of the composition is 100% by weight.

[0129] The process for preparing dry granulated tablets comprises preparing a blend of ingredients by mixing the ingredients in a suitable order; compacting the mixture thus obtained to form compacted shapes (i.e. preforms or slugs); sieving the compacted shapes to obtain granules; and finally compressing the obtained granules into tablets.

[0130] The manufacturing conditions of the method for pressing into tablets as defined above can be easily determined by a person skilled in the art. In one embodiment, the pressing step is carried out under pressure to obtain a tablet having a hardness of 50N to 150N, particularly 70N to 100N, more particularly about 80N, to obtain a tablet having a weight of about 200 to 600 mg.

[0131] Both methods disclosed above for preparing the solid composition of the present invention in tablet form comprising cannabinoid co-crystals are advantageous because the use of solvents, particularly organic solvents, is avoided and is carried out under mild manufacturing conditions. These methods are therefore particularly advantageous for avoiding degradation of cannabinoids during the manufacture of the solid composition and during its storage.

[0132] In one embodiment, the pharmaceutical composition is a capsule. In one embodiment, the pharmaceutical composition is a hard capsule. In one embodiment, the pharmaceutical composition is a hard capsule selected from a hard gelatin capsule and a hydroxypropylmethylcellulose (HMPC) hard capsule.

[0133] In one embodiment, the pharmaceutical capsule comprises:

[0134] 1 to 80% by weight of one or more cannabinoid co-crystals;

[0135] 20 to 99 weight percent of one or more fillers; and

[0136] 0.25 to 10% by weight of one or more glidants;

[0137] The sum of the components of the composition is 100% by weight.

[0138] In one embodiment, the pharmaceutical capsule comprises:

[0139] 10 to 40% by weight of one or more cannabinoid co-crystals;

[0140] 55 to 90 weight percent of one or more fillers; and

[0141] 0.25 to 10% by weight of one or more glidants;

[0142] The sum of the components of the composition is 100% by weight.

[0143] In one embodiment, the pharmaceutical capsule comprises:

[0144] 10 to 40% by weight of one or more cannabinoid co-crystals;

[0145] 60 to 90% by weight microcrystalline cellulose; and

[0146] 0.25 to 2% by weight of magnesium stearate;

[0147] The sum of the components of the composition is 100% by weight.

[0148] The capsules as defined above can be prepared by any capsule filling method known in the art. Thus, the method for preparing a capsule comprises: (a) preparing a blend of ingredients by mixing the ingredients in an appropriate order; (b) filling a pharmaceutical capsule with the blend obtained in step (a); and (c) sealing the pharmaceutical capsule.

[0149] In one embodiment, the pharmaceutical composition is a "chewable" composition. The term "chewable" refers to a composition that is broken and chewed between the teeth before ingestion. Typically, a chewable composition comprises a gum base core, optionally coated. The core often comprises an insoluble gum selected from the group consisting of fillers, waxes, antioxidants, sweeteners, and flavorings. In one embodiment, the pharmaceutical composition is a "chewable" tablet.

[0150] In one embodiment, the solid composition is an unsupported composition. The term "unsupported" refers to a composition in which the cannabinoid is not absorbed or adsorbed onto the surface of the solid support.

[0151] The term "co-crystal" refers herein to a crystalline entity having at least two different components (also referred to as "coformers") that form a unit cell at room temperature (20-25°C) and interact through weak interactions. Thus, in a co-crystal, one component crystallizes together with one or more neutral components. A co-crystal may contain one or more solvent molecules in the crystal lattice. In other words, the term co-crystal refers to a solid of a crystalline single-phase material composed of two or more different molecules and / or ionic compounds, usually in a stoichiometric ratio that is neither a solvate nor a simple salt (see Indian J. Pharm. Sci. 2017, Vol. 79 (6), pp. 858-871).

[0152] In one embodiment, the solid composition comprises co-crystals having a particle size of 50 μm to 250 μm, in particular 100 μm to 200 μm. In one embodiment, the solid composition comprises co-crystals having a D50 of 50 μm to 250 μm, in particular 100 μm to 200 μm. These particle sizes allow the solid composition of the present invention to be prepared by a simple, cost-effective and industrially scalable method without compromising the stability of the cannabinoids in the composition or the stability and uniformity of the solid composition itself. The term "particle size" refers to the size of the co-crystal measured in μm. The measurement is performed by conventional analytical techniques with appropriate equipment, such as microscopic determination using a scanning electron microscope (SEM). In the present invention, the particle size is measured by a Mastersizer 2000 particle size analyzer. Such an instrument uses a laser diffraction technique to measure the size of the particles. It works by measuring the intensity of the scattered light as the laser beam passes through a dispersed particle sample. The data is then analyzed using a general model to calculate the size of the particles that generate the scattering pattern, assuming a spherical particle shape. The terms "particle size distribution" or "PSD" have the same meaning and are used interchangeably. They refer to the percentage of co-crystals within a certain size range. The term "D50" refers to the particle size distribution value where at least 50% of the co-crystals have a size less than or equal to a given value.

[0153] The term "cannabinoid" refers to a class of compounds with various affinities for the endocannabinoid receptors (CB1 and CB2). This group includes endocannabinoids (produced naturally by humans and animals), phytocannabinoids (found in cannabis and some other plants), and synthetic cannabinoids (made in whole or in part by artificial means), the most famous of which are THC and CBD. Cannabinoid compounds are characterized by poor oral bioavailability, especially THC and CBD. Cannabinoids are highly lipophilic and therefore have poor solubility both in vitro and in vivo. This fact, combined with certain pre-systemic events in the gastrointestinal (GI) tract and first-pass metabolism, also contributes to their poor bioavailability.

[0154] In one embodiment, the solid composition comprises a cannabinoid co-crystal that is oily or gelatinous at room temperature. The term "room temperature" refers to ambient temperature without heating or cooling, typically comprising 20°C to 25°C.

[0155] In one embodiment, the solid composition comprises a cannabinoid co-crystal, wherein the cannabinoid is obtainable from a plant of the genus Cannabis, such as Cannabis indica and Cannabis sativa, by an extraction process. In one embodiment, the solid composition comprises a cannabinoid co-crystal, wherein the cannabinoid is obtainable by a total synthesis or semi-synthesis process.

[0156] In one embodiment, the solid composition comprises one or more acceptable excipients or carriers and a co-crystal, wherein the cannabinoid is selected from the group consisting of tetrahydrocannabinol (THC), cannabidiol (CBD), cannabinol (CBN), cannabigerol (CBG), cannachromene (CBC), cannabicyclol (CBL), cannabinol (CBV), tetrahydrocannabinol (THCV), cannabichromevarin (CBDV), cannabichromevarin (CBCV), cannabigerovarin (CBGV), cannabigerovarin monomethyl ether (CBGM), Δ8-tetrahydrocannabinol (Δ8-THC), or isoforms, derivatives, precursors, metabolites thereof; the combination is any two or more of the listed cannabinoids.

[0157] In one embodiment, the solid composition comprises a co-crystal, wherein the cannabinoid is selected from the group consisting of tetrahydrocannabinol (THC), cannabinol (CBN), cannabigerol (CBG), cannabichromene (CBC), cannabicycline (CBL), cannabinol (CBV), tetrahydrocannabinol (THCV), cannabidiol (CBDV), cannabichromene (CBCV), cannabigerol (CBGV), cannabigerol monomethyl ether (CBGM), Δ8-tetrahydrocannabinol (Δ8-THC), or isoforms, derivatives, precursors, metabolites thereof; the combination is any two or more of the listed cannabinoids.

[0158] In one embodiment, the solid composition comprises co-crystals, wherein the cannabinoids are selected from the group consisting of tetrahydrocannabinol (THC), cannabidiol (CBD), Δ8-THC, cannabinol (CBN), cannabigerol (CBG), cannabidiol (CBDV), and mixtures thereof. In one embodiment, the solid composition comprises co-crystals, wherein the cannabinoids are selected from the group consisting of tetrahydrocannabinol (THC), cannabidiol (CBD), cannabinol (CBN), cannabigerol (CBG), cannabidiol (CBDV), and mixtures thereof. In one embodiment, the solid composition comprises co-crystals, wherein the cannabinoids are selected from the group consisting of tetrahydrocannabinol (THC), cannabidiol (CBD), Δ8-THC, and mixtures thereof. In one embodiment, the solid composition comprises co-crystals, wherein the cannabinoids are selected from the group consisting of tetrahydrocannabinol (THC), cannabidiol (CBD), and mixtures thereof. In one embodiment, the solid composition comprises a co-crystal, wherein the cannabinoid is selected from the group consisting of tetrahydrocannabinol (THC), Δ8-tetrahydrocannabinol (Δ8-THC), and mixtures thereof. In one embodiment, the solid composition comprises a co-crystal, wherein the cannabinoid is selected from the group consisting of tetrahydrocannabinol (THC).

[0159] In a specific embodiment, the solid composition comprises a co-crystal in which the cannabinoid is CBD. Cannabidiol (abbreviated as (-)-CBD or CBD) is the international non-proprietary name of 2-[(1R,6R)-6-isopropenyl-3-methylcyclohex-2-en-1-yl]-5-pentylbenzene-1,3-diol with CAS number 13956-29-1. The structure of cannabidiol corresponds to the following formula (I):

[0160]

[0161] In a specific embodiment, the solid composition comprises a co-crystal wherein the cannabinoid is THC. 9 -Tetrahydrocannabinol (abbreviated as Δ 9 -THC, (-)-Δ 9 -THC, trans-(-)-Δ 9 -THC or THC) is the international nonproprietary name of (-)-(6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,8,10a-tetrahydro-6H-benzo[c]chromene-1-ol with CAS number 1972-08-3. 9 -THC structure corresponds to the following formula (II):

[0162] In a specific embodiment, the solid composition comprises a co-crystal wherein the cannabinoid is Δ8-THC. 8 -THC, (-)-Δ 8 -THC, trans-(-)-Δ 8 -THC or delta8-THC) is the international nonproprietary name of (6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,10,10a-tetrahydro-6H-benzo[c]chromene-1-ol with CAS number 5957-75-5. 8 -THC has the following structure:

[0163]

[0164] In a specific embodiment, the solid composition comprises a co-crystal wherein the cannabinoid is CBN. Cannabinol (abbreviated as CBN) is the international nonproprietary name of 6,6,9-trimethyl-3-pentylbenzo[c]chromene-1-ol having a CAS number of 521-35-7. The structure of cannabinol corresponds to the following formula (IV):

[0165]

[0166]

[0167] In a specific embodiment, the solid composition comprises a co-crystal in which the cannabinoid is CBG. Cannabigerol (abbreviated as CBG) is the international non-proprietary name of 2-[(2E)-3,7-dimethylocta-2,6-diene-1-yl]-5-pentylbenzene-1,3-diol with CAS number 25654-31-3. Its structure corresponds to the following formula (V):

[0168]

[0169] In a specific embodiment, the solid composition comprises a co-crystal wherein the cannabinoid is CBDV. Cannabidiol (abbreviated as CBDV) is the international non-proprietary name of 2-((1R,6R)-3-methyl-6-(prop-1-en-2-yl)cyclohex-2-en-1-yl)-5-propylbenzene-1,3-diol with CAS number 24274-48-4. Its structure corresponds to the following formula (VI):

[0170]

[0171] As described above, the solid composition comprises zwitterions. The term "zwitterion" refers to a molecule having separate and distinct positively and negatively charged moieties residing on the same molecule and having a net charge of zero. Thus, the coformer comprises one or more charged functional groups. Without being bound by any theory, the presence of one or more protonatable groups in the coformer allows for increased solubility of the cannabinoid after dissociation from the co-crystal. Thus, the co-crystals of the present invention having one or more protonatable groups allow for altering the solubility of the cannabinoid under physiological conditions. This means that the co-crystals of the present invention comprising a water-soluble coformer (zwitterion) can produce a solubility improvement by forming a complex in solution, by dissociation of the co-crystal (if reprecipitation is not immediate) or by reprecipitation of a more soluble crystalline form.

[0172] In one embodiment, the zwitterion comprises a positively charged nitrogen atom and a negatively charged group distal to the positively charged nitrogen atom on the organic zwitterion and spaced apart by at least one carbon atom, preferably 1 to 4 carbon atoms. In one embodiment, the coformer is an amino acid.

[0173] In one embodiment, the solid composition comprises a co-crystal, wherein the coformer in the co-crystal is selected from the group consisting of L-proline, betaine, L-carnitine, D-proline and DL-proline. In particular, it is selected from the group consisting of L-proline, D-proline and DL-proline. In particular, it is selected from the group consisting of L-proline, betaine and L-carnitine.

[0174] In one embodiment, the solid composition comprises a co-crystal, wherein the cannabinoid is CBD, THC, Δ8-THC, CBN, CBG or CBVD and the coformer is selected from the group consisting of L-proline, betaine, L-carnitine, D-proline and DL-proline, in particular, selected from L-proline, D-proline, betaine and L-carnitine.

[0175] In one embodiment, the solid composition comprises a co-crystal, wherein the cannabinoid is THC or Δ8-THC, and the coformer is selected from the group consisting of L-proline, D-proline and DL-proline, more particularly selected from L-proline, D-proline, and more particularly L-proline.

[0176] In one embodiment, the solid composition comprises a co-crystal, wherein the cannabinoid is CBD, CBDV, CBG or CBN, and the coformer is selected from the group consisting of L-proline, D-proline and DL-proline, L-carnitine and betaine. In particular, it is selected from L-proline, D-proline, L-carnitine and betaine; more particularly betaine.

[0177] In one embodiment, the solid composition comprises co-crystal forms I, II, III, IV, V, VII, VIII, IX, X, XI, XII, XIII, XIV, XV, XVI, XVII, XVIII or XIX as defined herein above. In one embodiment, the solid composition comprises co-crystal forms I, II, III, IV, V, VII, VIII, IX and X as defined herein above. In particular, the solid composition comprises co-crystal forms I, VII, IX, XI, XII, XVI, XVII, XVIII and XIX. In particular, the solid composition comprises co-crystal forms I, VII, IX, XI and XII.

[0178] In particular, the solid composition comprises co-crystal forms I, VII and IX.

[0179] A second aspect of the invention relates to co-crystals of a cannabinoid selected from THC, Δ8-THC, CBN, CBG, CBDV and a zwitterionic coformer. In one embodiment, the co-crystal of the invention is a co-crystal wherein the coformer is selected from the group consisting of L-proline, betaine, L-carnitine, D-proline and DL-proline. The coformers L-proline, L-carnitine and betaine; more particularly L-proline, are particularly advantageous because they are useful for purification of the cannabinoid after dissociation from the co-crystal and for use as a drug-forming part of a pharmaceutical composition due to the fact that L-proline, L-carnitine and betaine are classified as Substance Added to Food by the FDA. In particular, the invention relates to co-crystal forms VII, VIII, IX, XI, XII, XIII, XVI, XVII, XVIII and XIX; more particularly VII, IX, XI, XIII, XIX. In one embodiment, the second aspect of the invention is a co-crystal of a cannabinoid selected from THC and Δ8-THC and a zwitterionic coformer. In one embodiment, the co-crystals of the invention are co-crystals of THC or Δ8-THC, wherein the coformer is selected from the group consisting of L-proline, D-proline. In particular, the co-crystals of the invention relate to co-crystal forms VII, VIII, IX and X; more particularly VII and IX.

[0180] In one embodiment, the solid composition comprises a co-crystal of 2-[(1R,6R)-6-isopropenyl-3-methylcyclohex-2-en-1-yl]-5-pentylbenzene-1,3-diphenol (CBD) and a co-former selected from the group consisting of L-proline, betaine, L-carnitine, D-proline and DL-proline. In particular, the co-crystal of the present invention comprised by the solid composition refers to co-crystal forms I, II, III, IV and V.

[0181] In one embodiment, the co-crystal is a co-crystal of CBD and L-proline, also referred to as Form I. For purposes of the present invention, L-proline is the International Nonproprietary Name (INN) of (S)-2-pyrrolidinecarboxylic acid and has CAS No. 147-85-3. The structure of L-proline is as follows:

[0182]

[0183] In one embodiment, co-crystal Form I is obtained by Cu-K α Its X-ray diffraction pattern under radiation comprises characteristic peaks at 5.8, 11.1 and 15.8 ± 0.3 2θ degrees. In one embodiment, co-crystal Form I is characterized by Cu-K αIts X-ray diffraction pattern under radiation is characterized by other characteristic peaks at 7.4, 11.4 and 21.2±0.3 2θ degrees.

[0184] More specifically, co-crystalline Form I is characterized by a pattern of peaks exhibited in an X-ray diffraction pattern, with the peaks expressed as degrees 2θ, 2θ (°), shown at Table 1 middle.

[0185] Table 1 : List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0186]

[0187]

[0188] Cocrystal Form I can be prepared by Figure 1 The X-ray diffraction patterns in were further characterized.

[0189] Cocrystal Form I can also be prepared by the following 1 H NMR spectrum (CD3OD, 400 MHz, δ) further characterized: 6.08 (s, 2H, ArH); 5.29 (s, 1H); 4.45 (d, 2H, J = 14.4 Hz); 3.98-3.90 (m, 2H); 3.42-3.35 (m, 1H); 3.26-3.19 (m, 1H); 2.94-2.87 (m, 1H); 2.38 (t, 2H, J=7.2Hz); 2.34-2.25(m,1H); 2.24-2.08(m,2H); 2.04-1.91(m,3H); 1.76-1.71(m,2H); 1.68(s,3H); 1.64(s,3H); 1.58-1.51(m,2H); 1.39-1.24(m,4H); 0.90(t,3H,J=7.2Hz).

[0190] Co-crystal Form I can also be prepared by Fig.11 The co-crystal Form I was further characterized by DSC (Differential Scanning Calorimetry) analysis as shown. DSC analysis of co-crystal Form I showed an endothermic event starting at 145.3°C corresponding to the melting point of co-crystal Form I, followed by an endothermic peak that may be due to a degradation (decomposition) event. Co-crystal Form I can also be further characterized by having a melting range of 142-152°C.

[0191] Co-crystal Form I can also be further characterized by thermogravimetric analysis (TGA). TG analysis of co-crystal Form I showed a weight loss between 26.7°C and 61.5°C, which corresponds to a loss of approximately 0.05 water molecules (0.20%, where the calculated value corresponding to one water molecule is 4.0%). Therefore, TGA confirms that co-crystal Form I is not a hydrate. Prior to its melting, TGA of co-crystal Form I showed no significant weight loss (see Figure 2 ).

[0192] Co-crystals of Form I prepared from pure commercial CBD (98.8% a / a HPLC - Method 1) had a purity equal to or greater than 99% a / a as measured by HPLC (Method 1). Notably, no coformers were detected under the HPLC conditions used for this analysis (Method 1).

[0193] Co-crystal Form I is in a 1:1 molar ratio (CBD:L-proline).

[0194] In one embodiment, the co-crystal is a co-crystal of CBD and betaine, also referred to as Form II. For purposes of the present invention, betaine is the International Nonproprietary Name (INN) of 2-trimethylammonioacetate and has CAS No. 107-43-7. The structure of betaine is as follows:

[0195]

[0196] In one embodiment, co-crystal Form II is obtained by Cu-K α Its X-ray diffraction pattern under radiation comprises characteristic peaks at 9.1, 10.7 and 18.4 ± 0.3 2θ degrees. In one embodiment, co-crystal Form II is characterized by Cu-K α Its X-ray diffraction pattern under radiation is characterized by other characteristic peaks at 5.3 and 13.0±0.3 2θ degrees.

[0197] More specifically, co-crystalline Form II is characterized by a pattern of peaks exhibited in an X-ray diffraction pattern, with the peaks expressed as degrees 2θ, 2θ (°), shown at Table 2 middle.

[0198] Table 2 : List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0199]

[0200]

[0201] Cocrystal Form II can be prepared by Figure 3 The X-ray diffraction patterns in were further characterized.

[0202] Cocrystal Form II can also be prepared by the following 1 H NMR spectrum (CD3OD, 400 MHz, δ) further characterized: 6.08 (s, 2H, ArH); 5.29 (s, 1H); 4.47-4.43 (m, 2H); 3.95-3.90 (m, 1H); 3.62 (s, 2H); 3.27 (s, 9H); 2.94-2.86 (m, 1H); 2.38 (t, 2H ,J=7.2Hz);2.25-2.15(m,1H);2.04-1.96(m,1H);1.76-1.71(m,2H);1.68(s, 3H); 1.64 (s, 3H); 1.59-1.51 (m, 2H); 1.38-1.24 (m, 4H); 0.90 (t, 3H, J = 7.2Hz).

[0203] Co-crystal Form II can also be further characterized by DSC (Differential Scanning Calorimetry) analysis.DSC analysis of co-crystal Form II showed endothermic events with onsets at 32.0°C, 79.2°C, 159.0°C and 233.0°C.

[0204] Co-crystals of Form II prepared from pure commercial CBD (98.8% a / a HPLC - Method 1) had a purity equal to or higher than 99% a / a as measured by HPLC (Method 1). Notably, no coformers were detected under the HPLC conditions used for this analysis.

[0205] Co-crystal Form II is in a 1:1 molar ratio (CBD:betaine).

[0206] In one embodiment, the co-crystal is a co-crystal of CBD and L-carnitine, also referred to as Form III. For purposes of the present invention, L-carnitine is the International Nonproprietary Name (INN) of (3R)-3-hydroxy-4-(trimethylammonio)butyrate (also referred to as 3-hydroxy-4-(trimethylazainium)butyrate) and has CAS No. 541-15-1. The structure of L-carnitine is as follows:

[0207]

[0208] In one embodiment, co-crystal Form III is obtained by Cu-K α Its X-ray diffraction pattern under radiation comprises characteristic peaks at 6.8, 11.3 and 20.0 ± 0.3 2θ degrees. In one embodiment, co-crystal Form III is characterized by Cu-K αIts X-ray diffraction pattern under radiation is characterized by other characteristic peaks at 12.7, 13.6 and 15.6 ± 0.3 2θ degrees.

[0209] More specifically, co-crystalline Form III is characterized by a pattern of peaks exhibited in an X-ray diffraction pattern, the peaks being expressed as degrees 2θ, 2θ (°), shown at Table 3 middle.

[0210] Table 3 : List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0211]

[0212]

[0213] Cocrystal Form III can be prepared by Figure 4 The X-ray diffraction patterns in were further characterized.

[0214] Cocrystal Form III can also be prepared by the following 1 H NMR spectrum (CD3OD, 400 MHz, δ) further characterized: 6.08 (s, 2H, ArH); 5.29 (s, 1H); 4.48-4.42 (m, 4H); 3.95-3.90 (m, 1H); 3.42-3.33 (m, 4H); 3.22 (s, 18H); 2.94-2.88 (m, 1H); 2.40-2.16 (m, 7H); 2.04-1.95 (m, 1H); 1.76-1.71 (m, 2H); 1.68 (s, 3H); 1.64 (s, 3H); 1.58-1.51 (m, 2H); 1.39-1.24 (m, 4H); 0.90 (t, 3H, J = 7.2 Hz).

[0215] Co-crystal form III can also be further characterized by DSC (differential scanning calorimetry) analysis. DSC analysis of co-crystal form III shows a first endothermic event starting at 56.4°C; a second endothermic event starting at 112.7°C; a third endothermic event starting at 138.7°C, and finally an endothermic event starting at 174.7°C. It was checked that the two first thermal events starting at 56.4 and 112.7°C did not correspond to melting events. The solids obtained after these two events corresponded to form III after rapid cooling to room temperature. Therefore, these events should correspond to the desorption and / or dehydration of water. In the case of dehydration, the crystalline form may lead to a dehydrated form with the same unit cell size as form III, or this dehydrated form may be converted to form III before XRPD analysis. The third event starting at 138.7°C corresponds to the solid-solid transition of form III to another crystalline form. Therefore, melting of co-crystal form III was not observed.

[0216] Co-crystals of Form III prepared from pure commercial CBD (98.8% a / a HPLC - Method 1) had a purity similar to that of the starting material. Notably, no coformer was detected under the HPLC conditions used for this analysis.

[0217] Co-crystal Form III is in a 1:2 molar ratio (CBD:L-carnitine).

[0218] In one embodiment, the co-crystal is a co-crystal of CBD and D-proline, also referred to as Form IV. For purposes of the present invention, D-proline is the International Nonproprietary Name (INN) of (R)-pyrrolidinecarboxylic acid and has CAS No. 344-25-2. The structure of D-proline is as follows:

[0219]

[0220] In one embodiment, co-crystal Form IV is obtained by Cu-K α Its X-ray diffraction pattern under radiation comprises characteristic peaks at 5.7, 11.2 and 15.7 ± 0.3 2θ degrees. In one embodiment, co-crystal Form IV is characterized by Cu-K α Its X-ray diffraction pattern under radiation is characterized by other characteristic peaks at 11.5 and 21.1±0.3 2θ degrees.

[0221] More specifically, co-crystalline Form IV is characterized by a pattern of peaks exhibited in an X-ray diffraction pattern, with the peaks expressed as degrees 2θ, 2θ (°), shown at Table 4 middle.

[0222] Table 4: List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0223]

[0224]

[0225] Cocrystal Form IV can be prepared by Figure 7 The X-ray diffraction patterns in were further characterized.

[0226] Cocrystal Form IV can also be prepared by the following 1 H NMR spectrum (CD3OD, 400 MHz, δ) further characterized: 6.08 (s, 2H, ArH); 5.29 (s, 1H); 4.45 (d, 2H, J = 14.2 Hz); 3.99-3.90 (m, 2H); 3.42-3.35 (m, 1H); 3.26-3.20 (m, 1H); 2.94-2.86 (m, 1H); 2.38 (t, 2H, J=7.7Hz); 2.35-2.25(m,1H); 2.24-2.08(m,2H); 2.02-1.92(m,3H); 1.77-1.71(m,2H); 1.68 (s, 3H); 1.64 (s, 3H); 1.59-1.51 (m, 2H); 1.39-1.25 (m, 4H); 0.90 (t, 3H, J = 7.0Hz).

[0227] Co-crystal Form IV can also be prepared by Figure 8 The co-crystal Form IV was further characterized by DSC (Differential Scanning Calorimetry) analysis as shown. DSC analysis of co-crystal Form IV showed an endothermic event starting at 154.0°C corresponding to the melting point of co-crystal Form IV, followed by an endothermic peak that may be due to a degradation (decomposition) event. Co-crystal Form IV can also be further characterized by having a melting range of 152-160°C.

[0228] Co-crystals of Form IV prepared from pure commercial CBD (98.8% a / a HPLC - Method 1) had a purity similar to that of the starting material. Notably, no coformers were detected under the HPLC conditions used for this analysis.

[0229] Co-crystal Form IV is in a 1:1 molar ratio (CBD:D-proline).

[0230] In one embodiment, the co-crystal is a co-crystal of CBD and DL-proline, also referred to as Form V. For purposes of the present invention, DL-proline is the International Nonproprietary Name (INN) of (rac)-pyrrolidinecarboxylic acid and has CAS No. 609-36-9. The structure of L-proline is as follows:

[0231]

[0232] In one embodiment, co-crystal Form V is obtained by Cu-K α Its X-ray diffraction pattern under radiation comprises characteristic peaks at 5.7, 11.1 and 15.7 ± 0.3 2θ degrees. In one embodiment, co-crystal Form V is characterized by Cu-K α Its X-ray diffraction pattern under radiation is characterized by other characteristic peaks at 11.4 and 21.0±0.3 2θ degrees.

[0233] More specifically, co-crystalline Form V is characterized by a pattern of peaks exhibited in an X-ray diffraction pattern, with the peaks expressed as degrees 2θ, 2θ (°), shown at Table 5 middle.

[0234] Table 5 : List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0235]

[0236]

[0237] Cocrystal Form V can be prepared by Figure 7 The X-ray diffraction patterns in were further characterized.

[0238] Cocrystal Form IV can also be prepared by the following 1 H NMR spectrum (CD3OD, 400 MHz, δ) further characterized: 6.08 (s, 2H, ArH); 5.29 (s, 1H); 4.45 (d, 2H, J = 14.1 Hz); 3.99-3.90 (m, 2H); 3.42-3.35 (m, 1H); 3.26-3.19 (m, 1H); 2.94-2.87 (m, 1H); 2.38 (t, 2H, J=7.7Hz); 2.35-2.25(m,1H); 2.24-2.08(m,2H); 2.02-1.92(m,3H); 1.77-1.71(m,2H); 1.68 (s, 3H); 1.64 (s, 3H); 1.59-1.51 (m, 2H); 1.39-1.25 (m, 4H); 0.90 (t, 3H, J = 7.0Hz).

[0239] Cocrystal Form V can also be prepared by Fig.10The co-crystal Form V was further characterized by DSC (Differential Scanning Calorimetry) analysis as shown. DSC analysis of co-crystal Form V showed an endothermic event starting at 130°C corresponding to the melting point of co-crystal Form V, followed by an endothermic peak that may be due to a degradation (decomposition) event. Co-crystal Form V can also be further characterized by having a melting range of 128-134°C.

[0240] Co-crystals of Form V prepared from pure commercial CBD (98.8% a / a HPLC - Method 1) had a purity similar to that of the starting material. Notably, no coformer was detected under the HPLC conditions used for this analysis.

[0241] Co-crystal Form V is in a 1:1 molar ratio (CBD:DL-proline).

[0242] In one embodiment, the co-crystal is a co-crystal of CBD and (2S, 3aS, 7aS)-octahydro-1H-indole-2-carboxylic acid, also referred to as Form VI. For purposes of the present invention, (2S, 3aS, 7aS)-octahydro-1H-indole-2-carboxylic acid has CAS No. 80875-98-5. The structure of (2S, 3aS, 7aS)-octahydro-1H-indole-2-carboxylic acid is as follows:

[0243] In one embodiment, Pass Cu-K α Its X-ray diffraction pattern under radiation comprises characteristic peaks at 4.4, 6.2 and 8.3 ± 0.3 2θ degrees. In one embodiment, co-crystal Form VI is characterized by Cu-K α Its X-ray diffraction pattern under radiation is characterized by other characteristic peaks at 10.0, 13.3 and 16.0±0.3 2θ degrees.

[0244] More specifically, co-crystalline Form VI is characterized by a pattern of peaks exhibited in an X-ray diffraction pattern, with the peaks expressed as degrees 2θ, 2θ (°), shown at Table 6 middle.

[0245] Table 6 : List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0246]

[0247]

[0248]

[0249] Cocrystal Form VI can be prepared by Fig.12The X-ray diffraction patterns in were further characterized.

[0250] Cocrystal Form IV can also be prepared by the following 1 H NMR spectrum (CD3OD, 400 MHz, δ) further characterized: 6.08 (s, 2H, ArH); 5.29 (s, 1H); 4.45 (d, 2H, J = 14.2 Hz); 4.01-3.91 (m, 2H); 3.67-3.63 (m, 1H); 2.94-2.87 (m, 1H); 2.41-2.31 (m, 4H); 2.27-2.15 (m, 1H); 2.12-2.05 (m, 1H); 2.04-1.96 (m, 1H); 1.93-1.84 (m, 1H); 1.81-1.61 (m, 11H); 1.59-1.25 (m, 10H); 0.90 (t, 3H, J = 7.0 Hz).

[0251] Cocrystal Form VI can also be prepared by Fig.13 The co-crystal Form VI was further characterized by DSC (Differential Scanning Calorimetry) analysis as shown. DSC analysis of co-crystal Form VI showed an endothermic event starting at 91°C corresponding to the melting point of co-crystal Form VI, followed by an endothermic peak that may be due to a degradation (decomposition) event. Co-crystal Form VI can also be further characterized by having a melting range of 90-100°C.

[0252] Co-crystals of Form VI prepared from pure commercial CBD (98.8% a / a HPLC - Method 1) had a purity similar to that of the starting material. Notably, no coformer was detected under the HPLC conditions used for this analysis.

[0253] Co-crystal Form V is in a 1:1 molar ratio (CBD:(2S,3aS,7aS)-octahydro-1H-indole-2-carboxylic acid).

[0254] In one embodiment, the co-crystal of the invention is a co-crystal of (-)-(6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,8,10a-tetrahydro-6H-benzo[c]chromen-1-ol and L-proline, also known as Form VII.

[0255] In one embodiment, the co-crystal Form VII of the present invention is obtained by Cu-K α Its X-ray diffraction pattern under radiation comprises characteristic peaks at 5.1, 11.5 and 20.5 ± 0.3 2θ degrees. In one embodiment, the co-crystal Form I of the present invention is characterized by Cu-K αIts X-ray diffraction pattern under radiation is characterized by other characteristic peaks at 10.3 and 15.5±0.3 2θ degrees.

[0256] More specifically, the co-crystalline Form VII of the present invention is characterized by a pattern of peaks exhibited in an X-ray diffraction pattern, the peaks being expressed as 2θ in degrees, 2θ (°), as shown in Table 7 middle.

[0257] Table 7 : List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0258]

[0259]

[0260] The co-crystal form VII of the present invention can be prepared by Fig.14 The X-ray diffraction patterns in were further characterized.

[0261] The co-crystal form VII of the present invention can also be prepared by the following 1 H NMR spectrum (CD3OD, 400 MHz, δ) further characterized: 6.42 (m, 1H, ArH); 6.15-6.07 (dd, 2H, J = 34.0, 1.7 Hz); 3.98-3.94 (dd, 1H, J = 8.7, 6.2 Hz); 3.41-3.35 (m, 1H); 3.25-3.19 (m, 1H); 3.16-3.13 (m, 1H); 2.4 1-2.37(t,2H); 2.34-2.25(m,1H); 2.15-2.07(m,3H); 2.00-1.90(m,3H); 1.65(m,3H); 1.6 8 (s, 3H); 1.61-1.51 (m, 3H); 1.45-1.25 (m, 10H); 1.04 (s, 3H); 0.89 (dd, 4H, J = 7.4, 6.6Hz).

[0262] The co-crystal form VII of the present invention can also be prepared by Fig.15 The co-crystal form VII is further characterized by DSC (differential scanning calorimetry) analysis as shown. DSC analysis of co-crystal form VII shows a first endothermic event starting at 50°C, followed by a second endothermic event corresponding to the melting of co-crystal form VII starting at about 109°C. The first event should correspond to the evaporation of residual solvent, because co-crystal form VII is still stable after heating until 75°C, and DSC experiments show that the event is irreversible. Co-crystal form VII of the present invention can also be further characterized by having a melting range of 109-120°C.

[0263] The co-crystal Form VII of the present invention is in a molar ratio of 1:1 (THC:L-proline).

[0264] In one embodiment, the co-crystal Form VII of the invention has a purity equal to or higher than 95% a / a as measured by GC.

[0265] In one embodiment, the co-crystal of the invention is a co-crystal of (-)-(6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,8,10a-tetrahydro-6H-benzo[c]chromen-1-ol and D-proline, also known as Form VIII.

[0266] In one embodiment, the co-crystal Form VIII of the present invention is obtained by Cu-K α Its X-ray diffraction pattern under radiation is characterized by containing characteristic peaks at 5.1, 11.4 and 20.6 ± 0.3 degrees 2θ.

[0267] More specifically, co-crystalline Form VIII of the present invention is characterized by a pattern of peaks exhibited in an X-ray diffraction pattern, the peaks being expressed as 2θ in degrees, 2θ (°), as shown in Table 8 middle.

[0268] Table 8 : List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0269]

[0270] The co-crystal form VII of the present invention can be prepared by Fig.16 The X-ray diffraction patterns in were further characterized.

[0271] The co-crystal form VIII of the present invention can also be prepared by the following 1 H NMR spectrum (CD3OD, 400 MHz, δ) further characterized: 6.42 (m, 1H, ArH); 6.15-6.07 (dd, 2H, J = 34.0, 1.7 Hz); 3.98-3.94 (dd, 1H, J = 8.7, 6.2 Hz); 3.41-3.35 (m, 1H); 3.25-3.19 (m, 1H); 3.16-3.13 (m, 1H); 2.4 1-2.37(t,2H); 2.34-2.25(m,1H); 2.15-2.07(m,3H); 2.00-1.90(m,3H); 1.65(m,3H); 1.6 8(s,3H);1.61-1.51(m,3H);1.45-1.25(m,10H);1.04(s,3H);0.89(dd,4H,J=7.4,6.6Hz).

[0272] The co-crystal form VIII of the present invention can also be prepared by Fig.17 The co-crystal Form VIII is further characterized by DSC (Differential Scanning Calorimetry) analysis as shown. DSC analysis of co-crystal Form VIII shows only one endothermic event starting at about 125°C, which should correspond to the melting of Form VIII. The co-crystal Form VIII of the present invention can also be further characterized by having a melting range of 125-141°C.

[0273] The co-crystal Form VIII of the present invention is in a 1:1 molar ratio (THC:D-proline).

[0274] In one embodiment, the co-crystal Form VIII of the invention has a purity equal to or higher than 95% a / a as measured by GC.

[0275] In one embodiment, the co-crystal of the invention is a co-crystal of Δ8-THC and L-proline, also referred to as Form IX.

[0276] In one embodiment, the co-crystal Form IX of the present invention is obtained by Cu-K α Its X-ray diffraction pattern under radiation comprises characteristic peaks at 5.1, 18.7 and 20.5 ± 0.3 degrees 2θ. In one embodiment, the co-crystal Form IX of the present invention is characterized by Cu-K α Its X-ray diffraction pattern under radiation is characterized by other characteristic peaks at 10.3, 15.5 and 21.9 ± 0.3 degrees 2θ.

[0277] More specifically, co-crystal Form IX of the present invention is characterized by the pattern of peaks exhibited in the X-ray diffraction pattern, with the peaks expressed as degrees 2θ, 2θ (°), shown in Table 9.

[0278] Table 9 : List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0279]

[0280]

[0281] The co-crystal Form IX of the present invention may be prepared by Fig.18 The X-ray diffraction patterns in were further characterized.

[0282] The co-crystal Form IX of the present invention is in a 1:1 molar ratio (Δ8-THC:L-proline).

[0283] In one embodiment, the co-crystal Form IX of the invention has a purity equal to or higher than 99.3% a / a as measured by GC.

[0284] In one embodiment, the co-crystal of the invention is a co-crystal of Δ8-THC and D-proline, also referred to as Form X.

[0285] In one embodiment, the co-crystal Form X of the present invention is obtained by Cu-K α Its X-ray diffraction pattern under radiation comprises characteristic peaks at 5.1, 16.1 and 20.4 ± 0.3 degrees 2θ. In one embodiment, the co-crystal Form IX of the present invention is characterized by Cu-K α Its X-ray diffraction pattern under radiation is characterized by other characteristic peaks at 10.1 and 21.7 ± 0.3 degrees 2θ.

[0286] More specifically, co-crystal Form X of the present invention is characterized by the pattern of peaks exhibited in the X-ray diffraction pattern, with the peaks expressed as degrees 2θ, 2θ (°), shown in Table 10.

[0287] Table 10: List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0288]

[0289]

[0290] The co-crystal Form X of the present invention can be prepared by Fig.19 The X-ray diffraction patterns in were further characterized.

[0291] The co-crystal Form X of the present invention is in a 1:1 molar ratio (Δ8-THC:D-proline).

[0292] In one embodiment, the co-crystal Form X of the invention has a purity equal to or higher than 96.4% a / a as measured by HPLC (Method 1).

[0293] In a specific embodiment, the solid composition comprises a cannabinoid in which the cannabinoid is a co-crystal of CBN and betaine, also referred to as Form XI.

[0294] In one embodiment, the co-crystal Form XI of the present invention is obtained by Cu-K α Its X-ray diffraction pattern under radiation comprises characteristic peaks at 6.3, 7.1 and 9.0 ± 0.3 degrees 2θ. Specifically, co-crystal Form XI of the present invention is characterized by the peak pattern exhibited in the X-ray diffraction pattern, the peaks are expressed as 2θ in degrees, 2θ (°), shown in Table 11.

[0295] Table 11: List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0296]

[0297]

[0298] The co-crystal form XI of the present invention may be prepared by Fig. 20 The X-ray diffraction patterns in were further characterized.

[0299] The co-crystal form XI of the present invention can also be prepared by the following 1 H NMR spectrum (CD3OD, 400 MHz, δ) further characterized: 8.36-8.33 (m, 1H); 7.13 (d, J = 7.8 Hz, 1H); 7.05-7.00 (m, 1H); 6.36 (d, J = 2.0 Hz, 1H); 6.26 (d, J = 2.0 Hz, 1H); 3.82 (s, 2H); 3.27 (s, 9H); 2.48 (t, J = 7.8 Hz, 2H); 2.34 (s, 3H); 1.67-1.55 (m, 2H); 1.54 (s, 6H); 1.43-1.27 (m, 4H); 0.92 (t, J = 7.0 Hz, 3H).

[0300] The co-crystal form XI of the present invention may also be prepared by Fig.21 The DSC (Differential Scanning Calorimetry) analysis shown was further characterized. The DSC analysis of co-crystal Form XI showed a first broad endothermic event starting at 50°C, which may be due to a dehydration event. Then, the endothermic peak starting at 93°C may correspond to a melting event. Therefore, DSC seems to indicate that co-crystal Form XI is a hydrate.

[0301] KF analysis of Form XI (11 mg) performed in duplicate gave a water content of 10.6% w / w, confirming that this form is a hydrate.

[0302] The co-crystal Form XI of the present invention is in a molar ratio of 1:1 (CBN:betaine).

[0303] In one embodiment, the co-crystal Form XI of the invention has a purity equal to or higher than 99.3% a / a as measured by HPLC (Method 2).

[0304] In a specific embodiment, the solid composition comprises wherein the cannabinoid is a co-crystal of CBN and L-proline, also referred to as Form XII.

[0305] In one embodiment, the co-crystal Form XII of the present invention is obtained by Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 6.3, 7.1 and 9.0 ± 0.3 degrees 2θ. Specifically, co-crystal Form XII of the present invention is characterized by the peak pattern exhibited in the X-ray diffraction pattern, the peaks are expressed as 2θ in degrees, 2θ (°), shown in Table 11.

[0306] Table 12: List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0307]

[0308]

[0309] The co-crystal form XII of the present invention can be prepared by Fig. 22 The X-ray diffraction patterns in were further characterized.

[0310] The co-crystal form XII of the present invention can also be prepared by the following 1 H NMR spectrum (CD3OD, 400 MHz, δ) further characterized: 8.17 (m, 1H); 7.15-7.13 (m, 1H), 7.07-7.05 (m, 1H); 6.43-6.42 (m, 1H); 6.31-6.30 (m, 1H); 4.06-4.02 (m, 1H); 3.45-3.27 (m, 2H); 2.50 (t, J = 7.8 Hz, 2H); 2.41-2.32 (m, 4H); 2.19-2.11 (m, 1H); 2.05-1.98 (m, 1H); 1.89-1.80 (m, 1H); 1.36-1.26 (m, 9H), 0.98 (t, J = 6.8 Hz, 3H).

[0311] The co-crystal form XII of the present invention can also be prepared by Fig.23 The DSC (differential scanning calorimetry) analysis shown was further characterized. The DSC analysis of co-crystal form XII showed a single endothermic event starting at 96°C, which may correspond to a melting event. Thus, the endothermic peak starting at 96°C may correspond to a melting event. Therefore, DSC confirmed that co-crystal form XII is not a hydrate.

[0312] The co-crystal Form XII of the present invention is in a molar ratio of 1:1 (CBN:L-proline).

[0313] In a specific embodiment, the solid composition comprises wherein the cannabinoid is a co-crystal of CBN and L-proline, also referred to as Form XIII.

[0314] In one embodiment, the co-crystal Form XIII of the present invention is obtained by Cu-K α Its X-ray diffraction pattern under radiation is characterized by comprising characteristic peaks at 4.7, 10.9 and 12.5 ± 0.3 degrees 2θ. Specifically, co-crystal Form XIII of the present invention is characterized by the peak pattern exhibited in the X-ray diffraction pattern, the peaks are expressed as 2θ in degrees, 2θ (°), shown in Table 11.

[0315] Table 13: List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0316]

[0317] The co-crystal form XIII of the present invention can be prepared by Fig.24 The X-ray diffraction patterns in were further characterized.

[0318] The co-crystal form XIII of the present invention can also be prepared by the following 1 H NMR spectrum (CD3OD, 400 MHz, δ) further characterized: 9.92 (s br, 1H); 8.29-8.25 (m, 1H); 7.17 (d, J = 7.8 Hz, 1H), 7.05-7.00 (dd, J = 1.6, 7.8 Hz, 1H); 6.39 (d, J = 1.6 Hz, 1H); 6.23 (d, J = 1.6 Hz, 1H), 3.62 (dd, J = 5.7, 8.6 Hz, 1H); 3.25-3.16 (m, 1H); 2.99 (dt, J=7.4, 11.3Hz, 1H); 2.43 (t, J=7.8Hz, 2H); 2.30 (s, 3H); 2.06-1.88 (m, 2H); 1.8 4-1.61(m,2H),1.59-1.49(m,2H);1.49(s,6H),1.37-1.20(m,4H),0.87(t,J=7.0HZ,3H).

[0319] The co-crystal form XIII of the present invention can also be prepared by Fig.25 The DSC (differential scanning calorimetry) analysis shown was further characterized. The DSC analysis of co-crystal form XIII showed a single endothermic event starting at 121 ° C, which may correspond to a melting event. Thus, the endothermic peak starting at 121 ° C may correspond to a melting event. Therefore, DSC confirmed that co-crystal form XIII is not a hydrate.

[0320] The co-crystal Form XIII of the present invention is in a molar ratio of 1:1 (CBN:L-proline).

[0321] In one embodiment, the co-crystal Form XIII of the invention has a purity equal to or higher than 91.5% a / a as measured by HPLC (Method 2).

[0322] In a specific embodiment, the solid composition comprises wherein the cannabinoid is a co-crystal of CBN and D-proline, also referred to as Form XIV.

[0323] In one embodiment, co-crystal Form XIV of the present invention is obtained by Cu-K α Its X-ray diffraction pattern under radiation is characterized by comprising characteristic peaks at 4.7, 10.9 and 12.5 ± 0.3 degrees 2θ. Specifically, co-crystal Form XIV of the present invention is characterized by the peak pattern exhibited in the X-ray diffraction pattern, the peaks are expressed as 2θ in degrees, 2θ (°), shown in Table 14.

[0324] Table 14: List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0325]

[0326]

[0327] Co-crystal Form XIV of the present invention may be prepared by Fig.26 The X-ray diffraction patterns in were further characterized.

[0328] The co-crystal form XIV of the present invention can also be prepared by the following 1 H NMR spectrum (CD3OD, 400 MHz, δ) further characterized: 11.42 (s br, 1H); 8.18-8.15 (m, 1H); 7.14 (d, J = 7.8 Hz, 1H), 7.08-7.04 (m, 1H); 6.43 (d, J = 1.6 Hz, 1H); 6.30 (d, J = 1.6 Hz, 1H); 4.04 (dd, J = 5.5, 8.6 Hz, 1H); 3.47-3.22 (m, 2H); 2.50 (t, J = 7 .8Hz,2H);2.38(s,3H);2.40-2.31(m,1H);2.19-2.08(m,1H);2.19-2.08(m,1H);2.08- 1.96 (m, 1H); 1.92-1.76 (m, 1H); 1.59 (s, 6H), 1.38-1.28 (m, 4H), 0.89 (t, J = 7.0HZ, 3H).

[0329] The co-crystal form XIV of the present invention can also be prepared by Fig. 27The DSC (Differential Scanning Calorimetry) analysis shown was further characterized. DSC analysis of co-crystal Form XIV showed a single endothermic event starting at 124°C, which may correspond to a melting event. Then, a small exothermic event (131°C) was observed that partially overlapped with the first endothermic event, the nature of which is unknown.

[0330] The co-crystal Form XIV of the present invention is in a 1:1 molar ratio (CBN:D-proline).

[0331] In one embodiment, the co-crystal Form XIV of the invention has a purity equal to or higher than 90.5% a / a as measured by HPLC (Method 2).

[0332] In a specific embodiment, the solid composition comprises wherein the cannabinoid is a co-crystal of CBN and D-proline, also referred to as Form XV.

[0333] In one embodiment, co-crystal Form XV of the present invention is obtained by Cu-K α Its X-ray diffraction pattern under radiation is characterized by comprising characteristic peaks at 5.1, 10.2 and 16.1 ± 0.3 degrees 2θ. Specifically, co-crystal Form XV of the present invention is characterized by the peak pattern exhibited in the X-ray diffraction pattern, the peaks are expressed as 2θ in degrees, 2θ (°), shown in Table 15.

[0334] Table 15: List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0335]

[0336] The co-crystal form XV of the present invention can be prepared by Fig.28 The X-ray diffraction patterns in were further characterized.

[0337] The co-crystal form XV of the present invention can also be prepared by the following 1 H NMR spectrum (CD3OD, 400 MHz, δ) further characterized: 8.17 (2, 1H); 7.15-7.13 (m, 1H), 7.07-7.05 (m, 1H); 6.43-6.42 (m, 1H); 6.31-6.30 (m, 1H); 4.09-4.02 (m, 1H); 3.45-3.27 (m, 2H); 2.50 (t, J=7.8 Hz, 2H); 2.41-2.32 (m, 4H); 2.19-2.11 (m, 1H); 2.08-1.97 (m, 1H); 1.89-1.80 (m, 1H); 1.34-1.23 (m, 9H), 0.91-0.85 (m, 3H).

[0338] The co-crystal form XV of the present invention can also be prepared by Fig.29 The co-crystal Form XV was further characterized by DSC (Differential Scanning Calorimetry) analysis as shown.DSC analysis of co-crystal Form XV showed a single endothermic event at 116°C, which likely corresponds to melting.

[0339] The co-crystal Form XV of the present invention is in a 1:1 molar ratio (CBN:D-proline).

[0340] In a specific embodiment, the solid composition comprises a co-crystal wherein the cannabinoid is CBG.

[0341] In one specific embodiment, the solid composition comprises a co-crystal wherein the cannabinoid is CBG and betaine, also referred to as Form XVI.

[0342] In one embodiment, the co-crystal Form XVI of the present invention is obtained by Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 7.8, 15.8 and 23.8 ± 0.3 degrees 2θ. Specifically, the co-crystal form XVI of the present invention is characterized by Cu-K α Its X-ray diffraction pattern under radiation contains other characteristic peaks at 18.0, 18.5 and 23.5 ± 0.32θ degrees. More specifically, co-crystalline form XVI of the present invention is characterized by the peak pattern exhibited in the X-ray diffraction pattern, the peaks are expressed as 2θ in degrees, 2θ (°), shown in Table 16.

[0343] Table 16: List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0344]

[0345]

[0346] Co-crystal Form XVI of the present invention may be prepared by Fig.30 The X-ray diffraction patterns in were further characterized.

[0347] The co-crystal form XVI of the present invention can also be prepared by the following method: 1H NMR spectrum (CD3OD, 400 MHz, δ) further characterized: 6.14 (s, 2H); 5.30-5.18 (m, 1H); 5.14-5.01 (m, 1H); 3.83 (s, 2H); 3.29-3.18 (m, 11H); 2.40 (t, 2H, J = 7.8 Hz); 2.11-2.00 (m, 2H); 1.98-1.88 (m, 2H); 1.75 (s, 3H); 1.66-1.48 (m, 8H); 1.40-1.23 (m, 4H); 0.90 (t, 3H, J = 7.0 Hz).

[0348] The co-crystal form XVI of the present invention may also be prepared by Fig.31 The DSC (differential scanning calorimetry) analysis shown was further characterized. The DSC analysis of co-crystal Form XVI showed an endothermic event starting at 77.2°C, which should correspond to the melting of the co-crystal. It is worth noting that the melting onset of Form XVI is higher than the melting onset observed for the CBG crystalline form (50.9°C).

[0349] The co-crystal Form XVI of the present invention is in a molar ratio of 1:1 (CBN:betaine).

[0350] In a specific embodiment, the solid composition comprises a co-crystal wherein the cannabinoid is CBG and L-carnitine, also referred to as Form XVII.

[0351] In one embodiment, the co-crystal Form XVII of the present invention is obtained by Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 7.0, 14.1 and 19.8 ± 0.3 degrees 2θ. Specifically, the co-crystal form XVII of the present invention is characterized by Cu-K α Its X-ray diffraction pattern under radiation contains other characteristic peaks at 17.6, 18.9 and 22.4 ± 0.3 degrees 2θ. More specifically, co-crystalline form XVII of the present invention is characterized by the peak pattern shown in the X-ray diffraction pattern, the peaks are expressed as 2θ in degrees, 2θ (°), shown in Table 17.

[0352] Table 17: List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0353]

[0354]

[0355] The co-crystal form XVII of the present invention can be prepared by Fig.32 The X-ray diffraction patterns in were further characterized.

[0356] The co-crystal form XVII of the present invention can also be prepared by the following 1 H NMR spectrum (CD3OD, 400 MHz, δ) further characterized: 6.14 (s, 2H); 5.29-5.18 (m, 1H); 5.12-5.02 (m, 1H); 4.51-4.39 (m, 1H); 3.44-3.07 (m, 13H); 2.48-2.26 (m, 4H); 2.12-1.99 (m, 2H); 1.98-1.87 (m, 2H); 1.75 (s, 3H); 1.70-1.49 (m, 8H); 1.43-1.23 (m, 4H); 0.90 (t, 3H, J = 7.0 Hz).

[0357] The co-crystal form XVII of the present invention can also be prepared by Fig.33 The DSC (differential scanning calorimetry) analysis shown was further characterized. The DSC analysis of co-crystal Form XVII showed an endothermic event starting at 71.4°C, which should correspond to the melting of the co-crystal. It is worth noting that the melting onset of Form XVII is higher than the melting onset observed for the CBG crystalline form (50.9°C).

[0358] The co-crystal Form XVII of the present invention is in a 1:1 molar ratio (CBN:L-carnitine).

[0359] In one embodiment, the co-crystal Form XVII of the invention has a purity equal to or higher than 96.5% a / a as measured by HPLC (Method 2).

[0360] In a specific embodiment, the solid composition comprises wherein the cannabinoid is a co-crystal of CBDV and L-proline, also referred to as Form XVIII.

[0361] In one embodiment, the co-crystal Form XVIII of the present invention is obtained by Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 6.1, 9.8 and 12.0 ± 0.3 degrees 2θ. Specifically, the co-crystal form XVIII of the present invention is characterized by Cu-K α Its X-ray diffraction pattern under radiation is characterized by comprising other characteristic peaks at 15.8 and 22.0 ± 0.3 degrees 2θ. More specifically, co-crystalline Form XVIII of the present invention is characterized by the peak pattern exhibited in the X-ray diffraction pattern, the peaks being expressed as 2θ in degrees, 2θ (°), as shown in Table 18.

[0362] Table 18: List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0363]

[0364]

[0365]

[0366] The co-crystal form XVIII of the present invention can be prepared by Fig.34 The X-ray diffraction patterns in were further characterized.

[0367] The co-crystal form XVIII of the present invention can also be prepared by the following 1 H NMR spectrum (DMSO·d6, 400 MHz) δ) was further characterized: 8.72 (s, 2H), 6.10–5.93 (m, 2H, ArH), 5.08 (s, 1H), 4.57–4.32 (m, 2H), 3.88–3.77 (d, J=8.4 Hz, 1H), 3.70–3.56 (dd, J=8.7, 5.7 Hz, 2H), 3.25–3.12 (m, 2H), 3.09–2.93 (m, 4H), 2.31–2.24 (m, 2H), 2.17–1.87 (m, 6H), 1.84–1.36 (m, 16H), 0.95–0.59 (m, 4H).

[0368] The co-crystal form XVIII of the present invention may also be prepared by Fig.35 The co-crystal Form XVIII was further characterized by DSC (Differential Scanning Calorimetry) analysis as shown. DSC analysis of co-crystal Form XVIII showed a first endothermic event starting at about 33°C, followed by a second endothermic event starting at about 157°C corresponding to the melting of co-crystal Form XVIII. The first event should correspond to the evaporation of residual solvent, because co-crystal Form XVIII was still stable after heating up to 90°C, and DSC experiments showed that this event was irreversible.

[0369] The co-crystal Form XVIII of the present invention is in a 1:1 molar ratio (CBDV:L-proline).

[0370] In one embodiment, the co-crystal Form XVIII of the invention has a purity equal to or higher than 99.0% a / a as measured by HPLC (Method 2).

[0371] In a specific embodiment, the solid composition comprises a co-crystal wherein the cannabinoid is CBDV and L-carnitine, also referred to as Form XIX.

[0372] In one embodiment, the co-crystal Form XIX of the present invention is obtained by Cu-K αIts X-ray diffraction pattern under radiation comprises characteristic peaks at 6.9, 10.6 and 11.1 ± 0.3 degrees 2θ. Specifically, the co-crystal Form XIX of the present invention is characterized by Cu-K α Its X-ray diffraction pattern under radiation is characterized by comprising other characteristic peaks at 13.7 and 14.5 ± 0.3 degrees 2θ. More specifically, co-crystal Form XIX of the present invention is characterized by the pattern of peaks exhibited in the X-ray diffraction pattern, the peaks being expressed as 2θ in degrees, 2θ (°), as shown in Table 19.

[0373] Table 19: List of selected peaks (only peaks with relative intensity greater than or equal to 1% are indicated):

[0374]

[0375]

[0376]

[0377] The co-crystal form XIX of the present invention can be prepared by Fig.36 The X-ray diffraction patterns in were further characterized.

[0378] The co-crystal form XIX of the present invention can also be prepared by the following 1 H NMR spectrum (DMSO·d6, 400 MHz, δ) further characterized: 8.74 (s, 2H), 6.16–5.90 (m, 2H, ArH), 5.08 (s, 1H), 4.62–4.32 (m, 2H), 4.25–4.09 (m, 1H), 3.87–3.73 (d, J=8.7 Hz, 1H), 3.25–2.95 (m, 12H), 2.32–2.24 (m, 2H), 2.10 (s, 1H), 2.02–1.87 (m, 2H), 1.86–1.73 (m, 1H), 1.72–1.31 (m, 10H), 0.87 (t, J=7.3 Hz, 3H).

[0379] The co-crystal form XIX of the present invention may also be prepared by Fig.37 The co-crystal Form XIX was further characterized by DSC (differential scanning calorimetry) analysis as shown. DSC analysis of co-crystal Form XIX showed a first endothermic event starting at about 34°C, followed by two overlapping endothermic events starting at about 180.2°C corresponding to melting and degradation of co-crystal Form XIX. The first event should correspond to the evaporation of residual solvent, because co-crystal Form XIX was still stable after heating up to 110°C, and DSC experiments showed that this event was irreversible.

[0380] The co-crystal Form XIX of the present invention is in a 1:1 molar ratio (CBDV:L-carnitine).

[0381] In one embodiment, the co-crystal Form XIX of the invention has a purity equal to or higher than 99.0% a / a as measured by HPLC (Method 2).

[0382] In one embodiment, the solid composition of the present invention comprises a co-crystal of CBD and a coformer selected from the group consisting of L-proline, D-proline, DL-proline; in particular, forms I, II, III, IV, V; more particularly, co-crystal forms I, IV and V; more particularly, co-crystal form I.

[0383] In one embodiment, the solid composition of the present invention comprises a co-crystal of THC and a coformer selected from the group consisting of L-proline and D-proline; particularly co-crystal Forms VII and VIII; more particularly co-crystal Form VII.

[0384] In one embodiment, the solid composition of the invention is a co-crystal of THC and a coformer selected from the group consisting of L-proline and D-proline; particularly co-crystal Forms VII and VIII; more particularly co-crystal Form VII.

[0385] In one embodiment, a solid composition of the invention comprises a co-crystal of Δ8-THC and a coformer selected from the group consisting of L-proline and D-proline; particularly co-crystal Forms IX and X; more particularly co-crystal Form IX.

[0386] In one embodiment, the solid composition of the invention is a co-crystal of Δ8-THC and a coformer selected from the group consisting of L-proline and D-proline; particularly co-crystal Forms IX and X; more particularly co-crystal Form IX.

[0387] In one embodiment, the solid composition of the present invention comprises co-crystals of CBN and a coformer selected from the group consisting of L-proline, D-proline and betaine; particularly co-crystal forms XI, XII, XIII, XIV and XV; more particularly co-crystal forms XI, XII and XIII.

[0388] In one embodiment, the solid composition of the present invention is a co-crystal of CBN and a coformer selected from the group consisting of L-proline, D-proline and betaine; particularly co-crystal forms XI, XII, XIII, XIV and XV; more particularly co-crystal forms XI, XII and XIII.

[0389] In one embodiment, the solid composition of the present invention comprises co-crystals of CBG and a coformer selected from the group consisting of betaine and L-carnitine; in particular co-crystal Forms XVI and XVII.

[0390] In one embodiment, the solid composition of the present invention is a co-crystal of CBG and a coformer selected from the group consisting of betaine and L-carnitine; in particular co-crystal Forms XVI and XVII.

[0391] In one embodiment, the solid composition of the present invention comprises co-crystals of CBDV and a coformer selected from the group consisting of betaine and L-carnitine; in particular co-crystal forms XVIII and XIX.

[0392] In one embodiment, the solid composition of the invention is a co-crystal of CBDV and a coformer selected from the group consisting of betaine and L-carnitine; in particular co-crystal forms XVIII and XIX.

[0393] A third aspect of the present invention is to provide a method for preparing the co-crystals as defined above, which refers to co-crystal forms I, II, III, IV, V, VI, VII, VIII, IX, X, XI, XII, XIII, XIV, XV, XVI, XVII, XVIII and XIX. The co-crystals of the present invention may be prepared in pure form or as a mixture. Any method disclosed in the prior art for preparing co-crystals may be used for the co-crystals of the present invention, such as wet grinding or slurrying.

[0394] The terms "wet milling" and "liquid-assisted milling" are equivalent and refer to techniques in which a few drops of a solvent are added to grind or grind the product or mixture. Neat milling and liquid-assisted milling are techniques that can be used to make co-crystals. In neat (dry) milling, the co-crystal formers are ground together manually using a mortar and pestle, using a ball mill, or using a vibrating mill. In liquid-assisted milling or kneading, a small or substoichiometric amount of liquid (solvent) is added to the grinding mixture.

[0395] The term "slurrying" as disclosed herein refers to any method of washing or dispersing by agitating a suspension of a compound with a solvent.

[0396] Thus, the method of preparing the co-crystals of the present invention comprises: (a) wet milling a mixture of a cannabinoid and a co-former in a solvent; and (b) drying the co-crystals thus obtained.

[0397] In one embodiment, step (a) is carried out in the presence of a solvent selected from the group consisting of: water; an organic solvent selected from (C5-C9)alkanes, (C1-C4)alcohols, (C1-C4)alkyl-CO-(C1-C4)alkyl, halogen-(C1-C4)alkanes, (C1-C4)alkyl-CO-O-(C1-C4)alkyl, cyclo(C5-C7)alkanes, phenyl-(C1-C4)alkyl, (C1-C4)-CN, H-CO-N((C1-C4)alkyl)2; and mixtures thereof. The term "alcohol" refers to an "alkane" in which at least one hydrogen atom is substituted by a hydroxyl group and contains the number of carbon atoms specified in the specification or claims. The term "alkane" refers to a saturated branched or straight-chain hydrocarbon containing the number of carbon atoms specified in the specification or claims. Examples include methanol, ethanol, n-propanol, isopropanol, butanol, isobutanol and sec-butanol. The term "alkyl" refers to a saturated straight or branched hydrocarbon chain containing the number of carbon atoms specified in the specification or claims. Examples include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl and tert-butyl groups, etc. The term "halogen-alkane" refers to an "alkane" in which at least one hydrogen atom is replaced by a halogen group and contains the number of carbon atoms specified in the specification or claims. Examples of halogen-alkanes include chloroform, trichloroethane and dichloroethane. The term cycloalkane refers to a "cyclic" alkane containing the number of carbon atoms specified in the specification or claims. The term cycloalkane includes carbocyclic alkanes or heterocyclic alkanes. The term "carbocyclic" alkane refers to a cycloalkane in which each member of the ring is a carbon atom. Examples of carbocyclic alkanes include cyclopentane and cyclohexane. The term "heterocyclic" alkane refers to a "carbocyclic" compound in which at least one carbon atom is replaced by an N, NH, O or S atom. Examples of heterocyclic alkanes include tetrahydrofuran and 1,4-dioxane. In one embodiment, step (a) is carried out in the presence of an organic solvent selected from the group consisting of (C5-C8)alkanes, (C1-C4)alcohols, (C1-C4)alkyl-CO-(C1-C4)alkyl, halogen-(C1-C4)alkanes, (C1-C4)alkyl-CO-O-(C1-C4)alkyl, cyclo(C5-C7)alkanes, phenyl-(C1-C4)alkyl, (C1-C4)-CN, H-CO-N((C1-C4)alkyl)2 and mixtures thereof. This method is particularly advantageous because it allows obtaining co-crystals in pure form.

[0398] In one embodiment, step (a) is carried out in the presence of heptane, water, acetonitrile, methanol, IPA, isobutanol, ethyl acetate, isobutyl acetate, methyl isobutyl ketone, dimethylformamide, 1,4-dioxane, dichloromethane, xylene, cyclohexane, heptane and mixtures thereof.

[0399] In one embodiment, when the co-crystal is co-crystal Form I, then step (a) is carried out in a solvent selected from the group consisting of water, acetonitrile, methanol, isobutyl acetate, methyl isobutyl ketone, dimethylformamide, 1,4-dioxane, dichloromethane, xylene and mixtures thereof.

[0400] In one embodiment, when the co-crystal is co-crystal Form II, step (a) is carried out in a solvent selected from the group consisting of (C1-C4)alkyl-CO-(C1-C4)alkyl, (C1-C4)alkyl-CO-O-(C1-C4)alkyl, cyclo(C5-C7)alkane, phenyl-(C1-C4)alkyl, H-CO-N((C1-C4)alkyl)2 and mixtures thereof.

[0401] In one embodiment, when the co-crystal is co-crystal Form III, then the solvent of step (a) is cyclo(C5-C7)alkane and mixtures thereof. In one embodiment, step (a) is cyclohexane and mixtures thereof.

[0402] In one embodiment, when the co-crystal is co-crystal Form IV, then the solvent of step (a) is (C5-C 12 )alkanes and mixtures thereof. In one embodiment, step (a) is heptane and mixtures thereof.

[0403] In one embodiment, when the co-crystal is co-crystal Form V, the solvent of step (a) is (C5-C 12 )alkanes and mixtures thereof. In one embodiment, step (a) is heptane and mixtures thereof.

[0404] In one embodiment, when the co-crystal is co-crystal Form VI, the solvent of step (a) is (C5-C 12 )alkanes and mixtures thereof. In one embodiment, step (a) is heptane and mixtures thereof.

[0405] In one embodiment, when the co-crystal is co-crystal Form XIX, then the solvent of step (a) is (C1-C4)alcohol, (C1-C4)alkyl-CO2(C1-C4)alkyl or a mixture thereof. In one embodiment, step (a) is isopropanol, ethyl acetate and a mixture thereof.

[0406] In one embodiment, when the co-crystal is a co-crystal selected from forms I, II, III, IV, V and VI, then the molar ratio between CBD and the coformer in step a) is from 2:1 to 1:2; preferably 1:1 for forms I, II, IV, V and VI, and preferably 1:2 for form VI.

[0407] In one embodiment, when the co-crystal is a co-crystal selected from XVIII and XIX, then the molar ratio between CBDV and the coformer in step a) is from 2:1 to 1:2; preferably 1:1.

[0408] The term "molar ratio" is used to refer to the molar stoichiometry of one compound relative to another compound. For example, the molar stoichiometry of one coformer of a cocrystal relative to another coformer. The molar ratio can be determined by 1 H NMR confirmed.

[0409] In one embodiment, step (a) is carried out at room temperature. In another embodiment, step (a) is carried out under vibration milling, in particular at a power of 15 Hz to 60 Hz, preferably 20 and 50 Hz, more preferably 5 and 35 Hz, in particular 30 Hz. The term "room temperature" refers to the ambient temperature without heating or cooling, typically from 20°C to 25°C.

[0410] In one embodiment, step (b) is carried out by drying the co-crystals thus obtained at room temperature, preferably under vacuum conditions. Typically, the vacuum involves a pressure of 0.5 to 3 mbar; preferably 1 to 2 mbar.

[0411] An alternative method of preparing the co-crystals of the present invention comprises: (c) slurrying the cannabinoid with the coformer and an organic solvent; and (d) isolating the co-crystals thereby obtained.

[0412] In one embodiment, step (c) is carried out in the presence of a solvent selected from the group consisting of (C1-C4) alcohol, (C1-C4) alkyl-CO-(C1-C4) alkyl, halogen-(C1-C4) alkane, (C1-C4) alkyl-CO-O-(C1-C4) alkyl, cyclo(C5-C7) alkane, phenyl-(C1-C4) alkyl, (C1-C4) alkyl-O-(C1-C4) alkyl, (C5-C8) alkane and mixtures thereof. In one embodiment, step (c) is carried out in the presence of a solvent selected from the group consisting of cyclohexane, ethanol, isopropanol, ethyl acetate, acetone, methyl isobutyl ketone, tetrahydrofuran, methyl tert-butyl ether, dichloromethane, heptane and toluene.

[0413] In one embodiment, when the co-crystal is co-crystal Form I, then step (c) is carried out in a solvent selected from the group consisting of (C1-C4) alcohols, cyclo(C5-C7) alkanes, (C5-C9) alkanes, aromatic alkanes, and mixtures thereof. In one embodiment, step c) is carried out in a solvent selected from the group consisting of cyclo(C5-C7) alkanes, (C5-C9) alkanes, (C1-C4) alcohols, and mixtures thereof. In one embodiment, step (c) is carried out in the presence of a solvent selected from the group consisting of EtOH and heptane, and mixtures thereof, preferably heptane.

[0414] In one embodiment, when the co-crystal is co-crystal Form II, then step (c) is carried out in a solvent selected from the group consisting of cyclo(C5-C7)alkanes, (C5-C9)alkanes and mixtures thereof, in particular cyclo(C5-C7)alkanes, (C5-C9)alkanes and mixtures thereof, preferably cyclohexane and heptane.

[0415] In one embodiment, when the co-crystal is co-crystal Form III, then step (c) is carried out in a solvent selected from the group consisting of cyclo(C5-C7)alkanes, (C5-C9)alkanes and mixtures thereof, in particular cyclo(C5-C7)alkanes, (C5-C9)alkanes and mixtures thereof, preferably cyclohexane and heptane.

[0416] In one embodiment, when the co-crystal is co-crystal Form IV, then step (c) is carried out in a solvent selected from the group consisting of (C1-C4)alcohols, cyclo(C5-C7)alkanes, (C5-C9)alkanes and mixtures thereof. In one embodiment, step c) is carried out in a solvent selected from the group consisting of cyclo(C5-C7)alkanes, (C5-C9)alkanes, (C1-C4)alcohols and mixtures thereof. In one embodiment, step (c) is carried out in the presence of a solvent selected from the group consisting of EtOH and heptane and mixtures thereof, preferably heptane.

[0417] In one embodiment, when the co-crystal is co-crystal Form V, then step (c) is carried out in a solvent selected from the group consisting of (C1-C4)alcohols, cyclo(C5-C7)alkanes, (C5-C9)alkanes, and mixtures thereof. In one embodiment, step c) is carried out in a solvent selected from the group consisting of cyclo(C5-C7)alkanes, (C5-C9)alkanes, (C1-C4)alcohols, and mixtures thereof. In one embodiment, step (c) is carried out in the presence of a solvent selected from the group consisting of EtOH and heptane, and mixtures thereof, preferably heptane.

[0418] In one embodiment, when the co-crystal is co-crystal Form VI, step (c) is carried out in a solvent selected from the group consisting of cyclo(C5-C7)alkanes, (C5-C9)alkanes and mixtures thereof; in one embodiment, step c) is carried out in a (C5-C9)alkane solvent, preferably heptane.

[0419] In one embodiment, when the co-crystal is co-crystal form VII and VIII, then step c) is carried out in (C1-C4)alkylCO(C1-C4)alkyl, (C5-C9)alkane, (C1-C4)alkylCOO(C1-C4)alkyl, acetonitrile and mixtures thereof. In one embodiment, step c) is carried out in a (C5-C9)alkane solvent, in particular heptane and mixtures thereof.

[0420] In one embodiment, when the co-crystal is co-crystal form IX and X, then step c) is carried out in (C1-C4)alkylCO(C1-C4)alkyl, (C1-C4)alcohol, (C5-C9)alkane, (C1-C4)alkylCOO(C1-C4)alkyl, acetonitrile and mixtures thereof. In one embodiment, step c) is carried out in a (C5-C9)alkane solvent, in particular heptane and mixtures thereof.

[0421] In one embodiment, when the co-crystal is co-crystal form XI-XV, then step c) is carried out in a solvent selected from the group consisting of cyclo(C5-C7)alkanes, (C5-C9)alkanes and mixtures thereof. In one embodiment, step c) is carried out in a (C5-C9)alkane solvent, preferably heptane.

[0422] In one embodiment, when the co-crystal is co-crystal form XVI-XVII, then step c) is carried out in a solvent selected from the group consisting of phenyl-(C1-C4)alkyl, cyclo(C5-C7)alkane, (C5-C9)alkane, (C1-C4)alcohol and mixtures thereof, preferably ethanol, toluene and heptane. In one embodiment, step c) is carried out in a (C5-C9)alkane solvent, more preferably heptane.

[0423] In one embodiment, when the co-crystal is co-crystal form XVIII-XIX, then step c) is carried out in a solvent selected from the group consisting of (C3-C5)alcohol, (C1-C4)alkyl-CO2(C1-C4)alkyl and mixtures thereof, preferably isopropanol, isobutanol and ethyl acetate.

[0424] In one embodiment, the organic solvent of step (c) in the method for preparing the co-crystal of the present invention is selected from the group consisting of cyclo(C5-C7)alkanes, (C5-C9)alkanes and mixtures thereof; provided that when the cannabinoid is 2-((1R,6R)-3-methyl-6-(prop-1-en-2-yl)cyclohex-2-enyl)-5-propylbenzene-1,3-diphenol, the organic solvent of step (c) is selected from the group consisting of (C3-C5)alcohols, (C1-C4)alkyl-CO2(C1-C4)alkyls and mixtures thereof. In one embodiment, the organic solvent of step (c) in the method for preparing the co-crystal of the present invention is heptane; provided that when the cannabinoid is 2-((1R,6R)-3-methyl-6-(prop-1-en-2-yl)cyclohex-2-enyl)-5-propylbenzene-1,3-diphenol, the organic solvent of step (c) is isopropanol, isobutanol and ethyl acetate.

[0425] In one embodiment, when the cannabinoid is CBD, THC, CBN, CBG and Δ8-THC, then step c) is carried out in cyclo(C5-C7)alkanes, (C5-C9)alkanes and mixtures thereof, particularly heptane. In one embodiment, when the co-crystal is co-crystal forms I-XVII, then step c) is carried out in cyclo(C5-C7)alkanes, (C5-C9)alkanes and mixtures thereof, particularly heptane. In one embodiment, when the cannabinoid is CBDV, then step c) is carried out in (C3-C5)alcohols, (C1-C4)alkyl-CO2(C1-C4)alkyl and mixtures thereof, particularly isopropanol, isobutanol and ethyl acetate. In one embodiment, when the co-crystal is co-crystal forms XVIII-XIX, then step c) is carried out in (C3-C5)alcohols, (C1-C4)alkyl-CO2(C1-C4)alkyl and mixtures thereof, particularly isopropanol, isobutanol and ethyl acetate. In one embodiment, when the co-crystal is co-crystal Form XVIII then step c) is carried out in isobutanol.In one embodiment, when the co-crystal is co-crystal Form XIX then step c) is carried out in isopropanol and ethyl acetate.

[0426] In one embodiment, the molar ratio between CBD and the coformer in step (c) is from 2:1 to 1:3; in particular, from 2:1 to 1:2; preferably, from 2:1 to 1:1. In a specific embodiment, when the co-crystal is co-crystal form I, the molar ratio between CBD and the coformer is 1:1; in particular, 1:0.6. In a specific embodiment, when the co-crystal is co-crystal form II, the molar ratio between CBD and the coformer is from 2:1 to 1:1; preferably, 2:1. In a specific embodiment, when the co-crystal is co-crystal form III, the molar ratio between CBD and the coformer is from 3:1 to 1:2; preferably, 3:1. In a specific embodiment, when the co-crystal is co-crystal form IV or form V, the molar ratio between CBD and the coformer is from 2:1 to 1:3; preferably, from 2:1 to 1:1. In a specific embodiment, when the co-crystal is co-crystal form IV, the molar ratio between CBD and the coformer is 1:0.5. In a particular embodiment, when the co-crystal is co-crystal Form VI, then the molar ratio between CBD and coformer is from 3:1 to 1:2; preferably 3:1.

[0427] In one embodiment, the molar ratio between THC and the coformer in step (c) is from 1:1 to 1:0.6; preferably from 1:1 to 1:0.6. In a specific embodiment, when the co-crystal is co-crystal Form VII, the molar ratio between THC and the coformer is 1:0.6. In a specific embodiment, when the co-crystal is co-crystal Form VIII, the molar ratio between THC and the coformer is 1:0.6.

[0428] In one embodiment, the molar ratio between Δ8-THC and the coformer in step (c) is from 1:1 to 1:0.4; in particular from 1:1 to 1:0.6. In a specific embodiment, when the co-crystal is co-crystal Form IX, the molar ratio between Δ8-THC and the coformer is 1:0.6. In a specific embodiment, when the co-crystal is co-crystal Form X, the molar ratio between Δ8-THC and the coformer is 1:0.6.

[0429] In one embodiment, when the co-crystal is a co-crystal selected from Forms XI, XII, XIII, XIV and XV, then the molar ratio between CBN and the coformer in step (c) is from 4:1 to 1:2; in particular 2:1.

[0430] In one embodiment, when the co-crystal is a co-crystal selected from forms XVI, XVII and XVIII, then the molar ratio between CBG and the coformer in step (c) is from 2:1 to 1:2; in particular 1:1.

[0431] In one embodiment, step (c) is carried out at room temperature. In another embodiment, step (c) is maintained with stirring overnight. The term "overnight" refers to a time interval of 10 h to 48 h, more preferably 20 h.

[0432] In one embodiment, step (c) is carried out under an inert atmosphere. The term "inert atmosphere" refers to an atmosphere having an oxygen content of no more than 500 ppm. In one embodiment, the inert atmosphere comprises one or more inert gases selected from the group consisting of nitrogen, helium and argon; preferably nitrogen. This method is particularly advantageous because it allows obtaining the co-crystal in pure form, avoiding the risk of degradation of the cannabinoid, in particular THC, by oxidation or heating.

[0433] In one embodiment, the separation step (d) may comprise removing the solvent, for example by one or more of the following operations: filtration, vacuum filtration, decantation and centrifugation, or other suitable techniques known to those skilled in the art. In one embodiment, step (d) is performed by filtering the solid followed by a washing step. In one embodiment, when the co-crystals are co-crystal forms I, II, III, IV, V and VI, the washing step is performed with a (C5-C8) alkane, in particular heptane. In one embodiment, step (d) is performed by filtering the solid followed by a washing step. In one embodiment, when the co-crystals are co-crystal forms VII and VIII, the washing step is performed with a (C5-C8) alkane, in particular heptane. In one embodiment, when the co-crystals are co-crystal forms IX and X, the washing step is performed with a (C5-C8) alkane, in particular heptane. In one embodiment, step (d) further comprises drying the separated co-crystals; preferably, the co-crystals are dried at room temperature, preferably under vacuum conditions. Typically, the vacuum involves a pressure of 0.5 mbar to 3 mbar. In one embodiment, when the co-crystal is co-crystal form XI-XIX, then the washing step is carried out with (C3-C5)alcohol or (C1-C4)alkyl-CO2(C1-C4)alkyl, preferably isopropanol, isobutanol and ethyl acetate.

[0434] In a particular embodiment, the mixture of step (a) or step (c) is seeded to initiate crystallization. In an embodiment, step (a) or step (c) is seeded with co-crystals of the invention, in particular co-crystal form I, co-crystal form II, co-crystal form III, co-crystal form IV, co-crystal form V, co-crystal form VI, co-crystal form VII and co-crystal form VIII. When the co-crystals are co-crystal forms I, II and III, the seed co-crystal form may be obtained by a wet milling method as shown in the Examples. When the co-crystals are co-crystal forms IV, V, VI, VII and VIII, the seed co-crystal form may be obtained by a slurrying method, for example as disclosed in the Examples. When the co-crystals are co-crystal forms IX and X, the seed co-crystal form may be obtained by a slurrying method, for example as disclosed in the Examples. When the co-crystals are co-crystal forms XI, XII, XIII, XIV, XV, XVI, XVII and XVIII, the seed co-crystal form may be obtained by a slurrying method, for example as disclosed in the Examples. When the co-crystal is co-crystal Form XIX, the seed co-crystal form may be obtained by a milling process, for example as disclosed in the Examples.

[0435] Also part of the present invention is a method of purifying a cannabinoid, the method comprising: (e) dissociating the co-crystal as defined above under such reaction conditions to obtain the cannabinoid; and (f) isolating the cannabinoid thus obtained.

[0436] In one embodiment, the purification method further comprises the previous step of preparing the co-crystal by the method as defined above in the second aspect of the invention, comprising performing steps (c) and (d); or performing steps (a) and (b). All embodiments disclosed above for steps (a), (b), (c) and (d) are also applicable to the purification method of cannabinoids of the present invention, in particular for the purification of CBD, THC, Δ8-THC, CBN, CBG and CBDV; more particularly for the purification of THC, CBD, CBN and CBDV.

[0437] In one embodiment, step (e) is carried out by dissociating the cannabinoid co-crystals as defined above in an organic solvent, or in a mixture of water and one or more water-immiscible organic solvents, followed by separation of the phases of the two-phase mixture. Examples of organic solvents suitable for carrying out step (e) include (C1-C4) alkyl-CO-O-(C1-C4) alkyl, (C1-C4) alkyl-O-(C1-C4) alkyl, (C1-C4) alkyl-CO-(C1-C4) alkyl and (C1-C9) alkane, etc. The term "immiscible organic solvent" refers to an organic solvent that forms two phases when combined, which means that the mixture obtained thereby is "biphasic" under specific conditions of component concentration and temperature. In addition, the term "water-immiscible organic solvent" refers to an organic solvent that is capable of forming a two-phase with water at the temperature at which the reaction is carried out. The term "biphasic" as used herein refers to a reaction medium comprising two immiscible liquid phases, such as an aqueous phase and a water-immiscible organic solvent phase. The term "biphasic" may also be used to describe methods employing such a reaction medium. In one embodiment, in step (e), the water-immiscible organic solvent is selected from the group consisting of (C5-C9)alkanes, (C1-C4)alkyl-O-(C1-C4)alkyls, and mixtures thereof; preferably (C1-C9)alkanes. Examples of (C1-C9)alkanes include heptane, cyclohexane, pentane, and mixtures thereof, and the like.

[0438] In one embodiment, in step (e), when the co-crystal is co-crystal Form VII or VIII, the volume ratio between water and the water-immiscible organic solvent is from 1:2 to 1:3; preferably from 1:2 to 1:2.3. In a specific embodiment, when the co-crystal is co-crystal Form VII, the volume ratio between water and the water-immiscible organic solvent is from 1:2 to 1:3; preferably from 1:2 to 1:2.3. The term "volume ratio" is used to indicate the volume stoichiometry of one compound relative to another compound.

[0439] In one embodiment, in step (e), when the co-crystal is co-crystal form XI-XIX, the volume ratio between water and the water-immiscible organic solvent is 2:1 to 1:3; preferably 1:1 to 2:1. In a specific embodiment, when the co-crystal is co-crystal form XI, the volume ratio between water and the water-immiscible organic solvent is 1:2. In a specific embodiment, when the co-crystal is co-crystal form XIX, the volume ratio between water and the water-immiscible organic solvent is 1:1. The term "volume ratio" is used to indicate the volume stoichiometry of one compound relative to another compound.

[0440] The separation step (f) may comprise removing the solvent by evaporation to dryness, or after crystallization, for example by one or more of the following operations: filtration, vacuum filtration, decantation and centrifugation or other suitable techniques known to those skilled in the art to separate the cannabinoids, CBD, THC, Δ8-THC, CBN, CBG and CBD; more particularly THC or CDB, CBDV or CBN. In one embodiment, step (f) further comprises drying the separated co-crystals; preferably, the co-crystals are dried at room temperature, preferably under vacuum conditions. Typically, the vacuum involves a pressure of 0.5 mbar to 3 mbar.

[0441] In one embodiment, the method for purifying cannabinoids, CBD, THC, Δ8-THC, CBN, CBG and CBDV, more particularly CBD, THC, CBN or CBDV, comprises performing steps (e) and (f), and further comprises performing steps (c) and (d) before step (e) as defined above in the present invention. The method for purifying cannabinoids, CBD, THC, Δ8-THC, CBN, CBG and CBDV, more particularly CBD, THC, CBN or CBDV comprises performing steps (c), (d), (e) and (f) as defined above.

[0442] Throughout the specification and claims, the word "comprising" and variations of the word are not intended to exclude other technical features, additives, components or steps. In addition, the word "comprising" covers the situation of "consisting of..." Other objects, advantages and features of the present invention will become apparent to those skilled in the art after reviewing the specification, or can be learned by practicing the present invention. The following examples and drawings are provided as illustrations, which are not intended to limit the present invention. Reference symbols associated with the drawings and in parentheses in the claims are only used to attempt to increase the understandability of the claims and should not be interpreted as limiting the scope of the claims. In addition, the present invention covers all possible combinations of specific and preferred embodiments described herein.

[0443] Example

[0444] Proton NMR analyses were recorded in deuterated solvents on a Varian Mercury 400 MHz spectrometer equipped with a 5 mm broadband probe ATB 1H / 19F / X. Spectra were acquired by dissolving the samples in 0.7 mL of deuterated solvent.

[0445] X-ray powder diffraction (XRPD) measurements were performed under ambient conditions on a PANalytical X'Pert PRO θ-θ diffractometer with a reflection geometry of 240 mm, equipped with Cu Kα radiation and a PIXcel detector, operating at 45 kV and 40 mA. Each sample was mounted on a silicon stand with zero background and rotated at 0.25 rev / s during data collection. For the co-crystals of cannabinoids and THC used as starting materials, the angle range was 3.0-40.0 ° (2θ), the step size was 0.013 ° and the scanning speed was 0.328 ° / s (10.20 s / step); while for the commercial CBD used as starting material and the purified CBD obtained after dissociation of the co-crystals of the present invention, the angle range was 3.0-30.0 ° (2θ), the step size was 0.013 ° and the scanning speed was 0.082 ° / s (40.80 s / step).

[0446] DSC analysis was recorded with a Mettler Toledo DSC2. For co-crystal forms I-VIII and XI-XIX, samples were weighed into a 40 μL aluminum crucible with a pinhole cover and heated from 25°C to 300°C at a rate of 10°C / min under nitrogen (50 mL / min). For co-crystal forms VII and VIII, samples were weighed into a 40 μL aluminum crucible with a pinhole cover and heated from 25°C to 150°C at a rate of 10°C / min under nitrogen (50 mL / min).

[0447] HPLC analyses were recorded using an Agilent 1100 HPLC system equipped with a vacuum degasser (G1322A), a quaternary pump (G1311A), an autosampler (G1313A) and a UV detector (G1314A). Different conditions were used depending on the experiment:

[0448] Method 1: Using a Zorbax Eclipse XDB-C18 column, 150 x 4.6 mm, 5 μm, the sample (5 mg) was dissolved in methanol (5 mL) and injected (1 μL) for HPLC measurement under isocratic conditions (ACN:water 80:20) with a detector at 225 nm.

[0449] Method 2: Use Kinetex EVO C18 column; 2.6 μm; 50x4.6 mm. The sample (5 mg) was dissolved in methanol (5 mL) and injected (1 μL). HPLC measurement was performed at 40°C with a detector at 210 nm and mobile phase A: ACN and B: water (flow rate 1.2 mL / min) according to the following gradient:

[0450] t(min) A(%) B(%) 0 45 55 12 45 55 17 0 100 25 0 100

[0451] Thermogravimetric analysis (TGA) was recorded in a Mettler Toledo TGA / SDTA851 thermogravimetric analyzer. The sample was weighed into a 100 μL aluminum crucible and sealed with a lid. The lid was automatically closed by a robot just before analysis. The sample was heated from 25°C to 300°C at 10°C / min under nitrogen (50 mL / min).

[0452] Karl Fischer (KF) analyses were recorded on a Metrohm 870KF Titrino Plus. Samples were analyzed in duplicate using the following reactants: Aquametric complex 5 (Panreac Ref. 285812.1610), anhydrous methanol (Panreac Ref. 481091.1611), and Karl Fischer water standard 1.0 mg / g (Panreac Ref. 395459.2527; used for calculation factors).

[0453] GC (gas chromatography) analysis was recorded in an Agilent 6890N system equipped with an autosampler injector (G2613A) and a flame ionization detector (G1530N). An HP-5 column, 30 m, 0.2 mm ID, 0.33 μm was used. The sample (5 mg THC equivalent) was dissolved in methanol (5 mL) and injected (2 μL) for GC measurement (injector temperature 220 ° C, detector temperature 300 ° C, split ratio 50: 1, flow rate 3 mL / min, carrier gas He, initial temperature 200 ° C, for 1 min, first temperature ramp (rate 10 ° / min, final temperature 220 ° C, for 5 min), second temperature ramp (25 ° C / min, final temperature 300 ° C, for 5 min)).

[0454] CBD used as starting material obtained by the extraction process is commercially available (CBDepot sro). A cannabis fraction containing about 50% w / w CBD used as starting material is also commercially available (CBDepot sro). L-proline (TCI), L-proline hydrate (obtained by exposing L-proline to moisture), betaine (Sigma), L-carnitine (TCI), D-proline (TCI), DL-proline (TCI) and (2S, 3aS, 7aS)-octahydro-1H-indole-2-carboxylic acid (TCI) used as starting materials are also commercially available.

[0455] Tablet hardness was recorded in a Heberlein-Schleuniger 5Yi hardness tester, and 5 tablets comprising co-crystal Form I of the present invention were tested according to the method disclosed in section 2.9.8 of the 9th edition of the European Pharmacopoeia (Ph. Eur, 2019).

[0456] Tablet disintegration testing was performed in a type A disintegration apparatus according to the European Pharmacopoeia according to the method disclosed in section 2.9.1 of the 9th edition of the European Pharmacopoeia (Ph. Eur, 2019). Six tablets containing co-crystal form I of the present invention were tested using deionized water at 37°C as the disintegration medium.

[0457] 1. Solid oral composition

[0458] 1.1. Capsules

[0459] 1.1.1.CBD hard capsules

[0460] 1.1.1.1. Composition

[0461] The qualitative and quantitative composition of the hard gelatin capsule containing the co-crystal Form I according to the invention obtained in Example 2.1 is as follows:

[0462]

[0463] (1) 101 is microcrystalline cellulose commercially available from JRS Pharma

[0464] 1.1.1.2. Preparation method

[0465] A) Preparation of powdered mixture

[0466] The amounts of co-crystal Form I of the invention, microcrystalline cellulose and magnesium stearate as defined in the previous table were mixed manually.

[0467] B) Capsule filling

[0468] Green / green hard gelatin capsules size 1 are manually filled with 200 mg of the powdered mixture obtained in part a) per capsule.

[0469] 1.1.2.THC hard capsules

[0470] 1.1.2.1. Composition

[0471] The qualitative and quantitative composition of the hard gelatin capsule containing the cocrystal form VII according to the invention obtained in Example 2.7 is as follows:

[0472]

[0473] (1) 101 is microcrystalline cellulose commercially available from JRS Pharma

[0474] 1.1.2.2. Preparation method

[0475] A) Preparation of powdered mixture

[0476] The amounts of co-crystal Form VII of the invention, microcrystalline cellulose and magnesium stearate as defined in the previous table were mixed manually.

[0477] B) Capsule filling

[0478] Green / green hard gelatin capsules size 1 are manually filled with 200 mg of the powdered mixture obtained in part a) per capsule.

[0479] 1.2. Tablets

[0480] 1.2.1. CBD tablets

[0481] 1.2.1.1. Composition

[0482] The qualitative and quantitative composition of the tablet containing the co-crystal Form I according to the invention obtained in Example 2.1 is as follows:

[0483]

[0484] (1) 101 is microcrystalline cellulose commercially available from JRS Pharma

[0485] (2) is croscarmellose sodium commercially available from JRS Pharma

[0486] 1.2.1.2. Preparation method

[0487] A) Preparation of powdered mixture

[0488] The amounts of co-crystal Form I of the invention, microcrystalline cellulose and magnesium stearate as defined in the previous table were mixed manually.

[0489] To the resulting blend, croscarmellose and talc are added; the resulting mixture is then blended in a double cone mixer (eg, double cone mixer Glatt SG17) at 20 rpm for 10 minutes.

[0490] B) Compaction

[0491] The resulting blend obtained in step (a) is compacted into a preform (ie a blank) on an eccentric press (eg eccentric press Bonals CO5) using a 19x10 mm capsule-shaped punch.

[0492] C) Tablet Compression

[0493] The resulting preform obtained in step b) is sieved through a 0.8 mm screen to obtain granules, which are compressed into tablets on an eccentric press (e.g., eccentric press Bonals CO5) using 17x8.5 mm rectangular biconvex punches. The tablets thus obtained have the following parameters:

[0494] Tablet weight 550mg Tablet weight difference limit 522.5 mg to 577.5 mg hardness 70N to 100N Disintegration time of tablets in water at 37°C Less than 15 minutes Number of pieces 44

[0495] The X-ray diffraction pattern (XRPD) of the CBD tablet thus obtained showed that Figure 1 The CBD co-crystal Form I disclosed in maintains its integrity after its formulation.

[0496] 1.2.2. THC tablets

[0497] 1.2.2.1. Composition

[0498] The qualitative and quantitative composition of the tablet containing the co-crystal form VII according to the invention obtained in Example 2.7 is as follows:

[0499]

[0500] (1) 101 is microcrystalline cellulose commercially available from JRS Pharma

[0501] 1.2.2.2. Preparation method

[0502] A) Preparation of powdered mixture

[0503] The amounts of co-crystal Form VII of the invention, microcrystalline cellulose and magnesium stearate as defined in the previous table were mixed manually.

[0504] B) Tablet Compression

[0505] The resulting blend obtained in step (a) is compressed into tablets on an eccentric press (eg, eccentric press Bonals CO5) using 9 mm biconvex tablet punches. The tablets thus obtained have a hardness ranging from 72N to 98N.

[0506] The X-ray diffraction pattern (XRPD) of the CBD tablet thus obtained showed that Fig.14 The THC co-crystal Form VII disclosed in maintains its integrity after its formulation.

[0507] 1.2.3. CBN tablets

[0508] 1.2.3.1. Composition

[0509] The qualitative and quantitative composition of the tablet containing the co-crystal form XI according to the invention obtained in Example 2.11 is as follows:

[0510]

[0511] (1) 101 is microcrystalline cellulose commercially available from JRS Pharma

[0512] (2) is croscarmellose sodium commercially available from JRS Pharma

[0513] 1.2.3.2. Preparation method

[0514] Tablets 1 and 2 were prepared by direct compression

[0515] A) Preparation of powdered mixture

[0516] The amounts of co-crystal Form XI of the present invention, microcrystalline cellulose and magnesium stearate as defined in the previous table were mixed manually.

[0517] B) Tablet Compression

[0518] The resulting blend obtained in step (a) is compressed into tablets on an eccentric press (eg, Eccentric Press Bonals) using 9 mm cylindrical biconvex tablet punches.

[0519] Preparation of tablets by dry granulation method 3

[0520] A) Preparation of powdered mixture

[0521] The amounts of co-crystal Form XI of the present invention, microcrystalline cellulose and croscarmellose as defined in the previous table were mixed manually.

[0522] B) Compaction

[0523] The resulting blend obtained in step (a) is compacted into a preform (ie a blank) on an eccentric press (eg, eccentric press Bonals) using a 19x10 mm capsule-shaped biconvex punch.

[0524] C) Tablet Compression

[0525] The generated preform obtained in step b) is sieved through a 0.8 mm screen to obtain granules. Talc and magnesium stearate are added to the generated granules and mixed manually. The generated mixture is then pressed into tablets using a 17x8.5 mm rectangular biconvex punch on an eccentric press (e.g., eccentric press Bonals).

[0526] Preparation of tablets by dry granulation 4

[0527] A) Preparation of powdered mixture

[0528] The amounts of co-crystal Form XI of the present invention, lactose monohydrate and croscarmellose as defined in the previous table were mixed manually.

[0529] B) Compaction

[0530] The resulting blend obtained in step (a) is compacted into a preform (ie a blank) on an eccentric press (eg, eccentric press Bonals) using a 19x10 mm capsule-shaped biconvex punch.

[0531] C) Tablet Compression

[0532] The generated preform obtained in step b) is sieved through a 0.8 mm screen to obtain granules. Talc and magnesium stearate are added to the generated granules and mixed manually. The generated mixture is then pressed into tablets using a 17x8.5 mm rectangular biconvex punch on an eccentric press (e.g., eccentric press Bonals).

[0533] 1.2.4. CBG tablets

[0534] 1.2.4.1. Composition

[0535] The qualitative and quantitative composition of the tablet containing the co-crystal form XVI according to the invention obtained in Example 2.16 is as follows:

[0536]

[0537] (3) 101 is microcrystalline cellulose commercially available from JRS Pharma

[0538] (4) is croscarmellose sodium commercially available from JRS Pharma

[0539] 1.2.4.2. Preparation method

[0540] Tablets 1 prepared by direct compression

[0541] A) Preparation of powdered mixture

[0542] The amounts of co-crystal Form XVI of the present invention, microcrystalline cellulose and magnesium stearate as defined in the previous table were mixed manually.

[0543] B) Tablet Compression

[0544] The resulting blend obtained in step (a) is compressed into tablets on an eccentric press (eg, Eccentric Press Bonals) using 9 mm cylindrical biconvex tablet punches.

[0545] Preparation of tablets by dry granulation 2

[0546] A) Preparation of powdered mixture

[0547] The amounts of co-crystal Form XVI of the present invention, microcrystalline cellulose and croscarmellose as defined in the previous table were mixed manually.

[0548] B) Compaction

[0549] The resulting blend obtained in step (a) is compacted into a preform (ie a blank) on an eccentric press (eg, eccentric press Bonals) using a 19x10 mm capsule-shaped biconvex punch.

[0550] C) Tablet Compression

[0551] The generated preform obtained in step b) is sieved through a 0.8 mm screen to obtain granules. Talc and magnesium stearate are added to the generated granules and mixed manually. The generated mixture is then pressed into tablets using a 17x8.5 mm rectangular biconvex punch on an eccentric press (e.g., eccentric press Bonals).

[0552] 1.2.5. CBDV tablets

[0553] 1.2.5.1. Composition

[0554] The qualitative and quantitative composition of the tablet containing the co-crystal form XIX according to the invention obtained in Example 2.19 is as follows:

[0555]

[0556] (5) 101 is microcrystalline cellulose commercially available from JRS Pharma

[0557] (6) is croscarmellose sodium commercially available from JRS Pharma

[0558] 1.2.5.2. Preparation method

[0559] Tablets 1 and 2 were prepared by direct compression

[0560] A) Preparation of powdered mixture

[0561] The amounts of co-crystal Form XIX of the invention and other excipients defined in the previous table were mixed manually.

[0562] B) Tablet Compression

[0563] The resulting blend obtained in step (a) is compressed into tablets on an eccentric press (eg, Eccentric Press Bonals) using 9 mm cylindrical biconvex tablet punches.

[0564] Preparation of tablets by dry granulation method 3

[0565] A) Preparation of powdered mixture

[0566] The amounts of co-crystal Form XIX of the present invention, microcrystalline cellulose and croscarmellose as defined in the previous table were mixed manually.

[0567] B) Compaction

[0568] The resulting blend obtained in step (a) is compacted into a preform (ie a blank) on an eccentric press (eg, eccentric press Bonals) using a 19x10 mm capsule-shaped biconvex punch.

[0569] C) Tablet Compression

[0570] The generated preform obtained in step b) is sieved through a 0.8 mm screen to obtain granules. Talc and magnesium stearate are added to the generated granules and mixed manually. The generated mixture is then pressed into tablets using a 17x8.5 mm rectangular biconvex punch on an eccentric press (e.g., eccentric press Bonals).

[0571] Preparation of tablets by dry granulation 4

[0572] A) Preparation of powdered mixture

[0573] The amounts of co-crystal Form XIX of the present invention, lactose monohydrate and croscarmellose as defined in the previous table were mixed manually.

[0574] B) Compaction

[0575] The resulting blend obtained in step (a) is compacted into a preform (ie a blank) on an eccentric press (eg, eccentric press Bonals) using a 19x10 mm capsule-shaped biconvex punch.

[0576] C) Tablet Compression

[0577] The generated preform obtained in step b) is sieved through a 0.8 mm screen to obtain granules. Talc and magnesium stearate are added to the generated granules and mixed manually. The generated mixture is then pressed into tablets using a 17x8.5 mm rectangular biconvex punch on an eccentric press (e.g., eccentric press Bonals).

[0578] 2. Co-crystals of cannabinoids

[0579] 2.1. Cocrystal Form I

[0580] · Preparation method using L-proline

[0581] A. Preparation by wet grinding

[0582] To a 2 mL Eppendorf tube containing CBD (20 mg, 0.064 mmol, 98.8% a / a HPLC - Method 1) was added L-proline (7.3 mg, 0.064 mmol, 1 eq.), 2 drops of acetonitrile and 3 stainless steel grinding balls, followed by grinding at 30 Hz for 45 minutes (3 cycles of 15 minutes) using a Retsch ball mill MM400. After drying under vacuum (about 1-2 mbar) at room temperature, the co-crystal Form I of the present invention was obtained as a white solid.

[0583] B. Preparation by pulping

[0584] B.1. Preparation of co-crystal Form I from high purity CBD by slurrying

[0585] To a round bottom flask equipped with magnetic stirring and N2 atmosphere and containing a mixture of CBD (1.00 g, 3.18 mmol, 1.5 eq., 98.8% a / a HPLC-method 1) and L-proline (244 mg, 2.120 mmol) was added heptane (20 mL). The resulting mixture was seeded with CBD.L-proline Form I and stirred for 15 hours at room temperature. The reaction was then monitored by XRPD analysis and additional amounts of CBD (584 mg, 1.85 mmol, 0.87 eq.) were added until complete conversion of L-proline was observed. The suspension was filtered through a sinter funnel (porosity n° 3) and washed with 3x 3,0 mL heptane. After drying in vacuo at room temperature, the co-crystal Form I according to the invention was obtained as a white solid (662 mg, 31%).

[0586] The co-crystal Form I thus obtained exhibited Figure 1 X-ray diffraction pattern (XRPD), such as Figure 2 The co-crystal Form I thus obtained also showed the above disclosed 1 H NMR and DSC spectra. TGA showed that it was not a stoichiometric hydrate.

[0587] B.2. Process for Purifying CBD from Cannabis Flower Extract by Co-crystallization of Form I

[0588] Preparation of cocrystal Form I

[0589] A hemp flower fraction (100 mg, 0.15 theoretical mmol; Figure 5 of1 H NMR spectrum A) and L-proline (18.3 mg, 0.159 mmol) were added to a round-bottom flask with heptane (1 mL). The resulting mixture was seeded with co-crystal form I of the present invention and stirred at room temperature for 15 hours. The suspension was filtered through a sintered funnel (porosity n°3) and washed with 3x 0.2 mL of heptane. After vacuum drying at room temperature, co-crystal form I containing traces of L-proline was obtained as a white solid (51 mg).

[0590] Dissociation of CBD from cocrystal Form I

[0591] The co-crystal Form I thus obtained was dissolved in 5 mL of a heptane:water (1:1) mixture, the heptane phase was washed with water (2 x 1 mL) and dried over anhydrous Na2SO4, and then the solvent was removed under reduced pressure and vacuum. CBD was thus recovered as a white pasty solid (35 mg, 35% overall yield, 50% maximum yield, 99.4% a / a HPLC-Method 1; Figure 5 of 1 H NMR spectrum B).

[0592] The CBD thus obtained showed an X-ray diffraction pattern (XRPD) (see Figure 6 The diffraction pattern B) and Figure 6 The pure commercial CBD in the diffraction spectrum A is the same. Cannabis flower extract containing about 50% w / w CBD was used as starting material and CBD recovered from co-crystallization of Form I (Example B.2.) was purified between the two purification processes. 1 Comparison of the HNMR spectrum and HPLC analysis indicated excellent purification (see also Purification Studies in Section 4 below).

[0593] B.3. Purification of the synthetic CBD by co-crystallization of Form I

[0594] Preparation of CBD

[0595] According to the synthesis method disclosed in Example 3 on page 80 of PCT patent application WO20061313941 and Example 8 on page 45 of PCT patent application WO2006053766, a crude CBD product having a purity of 62% a / a measured by GC was obtained.

[0596] Preparation of cocrystal Form I

[0597] To a round-bottom flask equipped with magnetic stirring and N2 atmosphere and containing a mixture of the crude CBD disclosed in the previous step (100 mg, 0.318 mmol; 62% a / a GC) and L-proline (18.3 mg, 0.159 mmol) was added heptane (15 mL). The resulting mixture was seeded with the co-crystal form I of the invention and stirred at room temperature for 15 hours. To the suspension thus obtained was added 0.5 mL of heptane, which was then filtered through a sintered funnel (porosity n°3) and washed with 3x 0.2 mL of heptane. After drying in vacuo at room temperature, a white solid corresponding to the co-crystal form I of the invention (84 mg) was obtained, which was a mixture with traces of L-proline (according to XRPD analysis).

[0598] Dissociation of CBD from cocrystal Form I

[0599] The co-crystal Form I thus obtained (69 mg) was dissolved in a mixture of heptane:water (2:1) at 120 V. After decantation, the aqueous phase was washed with heptane (3 x 20 V). The organic extracts were then recombined and washed with a saturated aqueous solution of NaCl and dried over anhydrous Na2SO4, and the solvent was then removed under reduced pressure and vacuum. CBD was thus recovered as a yellow oil (33 mg, 62% purity crude material, 93.13% a / a GC), showing an X-ray diffraction pattern (XRPD) with Figure 6 The diffraction spectrum A is the same as that of pure commercial CBD.

[0600] Impurity distribution of CBD

[0601] A comparative study of the impurity profiles of CBD used as starting material obtained by the synthesis methods disclosed in PCT patent applications WO20061313941 and WO2006053766 and having a purity of 62% a / a measured by GC, and CBD obtained after dissociation of co-crystal Form I of the present invention was performed.

[0602] The following table shows the impurity profile of these two CBDs measured by GC and expressed as % a / a:

[0603]

[0604] (1) Regio-CBD is the compound 4-[(1R,6R)-3-methyl-6-(1-methylvinyl)-2-cyclohexene-1-

[0605] The common name for 5-pentyl-1,3-benzenediol, also known as CBD

[0606] (2) Iso-THC is the common name for the compound iso-tetrahydrocannabinol

[0607] As shown in the table above, all major impurities of crude CBD were reduced after purification by co-crystallization according to GC analysis. Further purification steps by co-crystallization can lead to higher purity.

[0608] 2.2. Cocrystal Form II

[0609] Preparation method

[0610] A. Preparation by wet grinding

[0611] To a 2 mL Eppendorf tube containing CBD (20 mg, 0.064 mmol, 98.8% a / a HPLC - Method 1) was added betaine (9.3 mg, 0.064 mmol, 1 eq.), 2 drops of isobutyl acetate and 3 stainless steel grinding balls, followed by grinding at 30 Hz for 45 minutes (3 cycles of 15 minutes) using a Retsch ball mill MM 400. After drying under vacuum (about 1-2 mbar) at room temperature, the co-crystal Form II of the present invention was obtained as a white solid (quantitative yield).

[0612] B. Preparation by pulping

[0613] Heptane (0.5 mL) was added to a sealed tube equipped with magnetic stirring and N2 atmosphere containing a mixture of CBD (50 mg, 0.159 mmol, 2 eq., 98.8% a / a HPLC-Method 1) and betaine (9.3 mg, 0.080 mmol). The resulting mixture was seeded with co-crystal Form II of the present invention and stirred at room temperature for 15 hours. The suspension was filtered through a sintered funnel (porosity n°3) and washed with 2x 0.1 mL of heptane. After vacuum drying at room temperature, co-crystal Form II was obtained as a white solid (34 mg, 50%).

[0614] The co-crystal Form II thus obtained showed Figure 3 and it also shows the X-ray diffraction pattern (XRPD) disclosed above 1 H NMR and DSC spectra.

[0615] 2.3. Cocrystal Form III

[0616] Preparation method

[0617] A. Preparation by wet grinding

[0618] To a 2 mL Eppendorf tube containing CBD (20 mg, 0.064 mmol) was added L-carnitine (10.3 mg, 0.064 mmol, 1 eq.), 2 drops of cyclohexane and 3 stainless steel grinding balls, followed by grinding at 30 Hz for 45 minutes (3 cycles of 15 minutes) using a Retsch ball mill MM 400. After drying under vacuum (about 1-2 mbar) at room temperature, pure co-crystal Form III was obtained as a white solid.

[0619] B. Preparation by pulping

[0620] Heptane (3 mL) was added to a round-bottom flask equipped with magnetic stirring and containing a mixture of CBD (300 mg, 0.954 mmol, 98.8% a / a HPLC-Method 1) and L-carnitine (307 mg, 1.908 mmol, 2 eq.). The resulting mixture was seeded with co-crystal Form III and stirred at room temperature for 15 hours. The suspension was filtered through a sintered funnel (porosity n°3) and washed with 2 x 1.0 mL of heptane. After vacuum drying at room temperature, co-crystal Form III was obtained as a white solid (483 mg, 80%).

[0621] The co-crystal Form III thus obtained showed Figure 4 and it also shows the X-ray diffraction pattern (XRPD) disclosed above 1 H NMR and DSC spectra.

[0622] 2.4. Cocrystal Form IV

[0623] Preparation method of pulping from high-purity CBD

[0624] Heptane (4 mL) was added to a cylindrical vial equipped with magnetic stirring and N2 atmosphere containing a mixture of CBD (399 mg, 1.269 mmol, 2 eq.) and D-proline (74 mg, 0.643 mmol). The resulting mixture was stirred at room temperature overnight. Then, because the solvent was almost completely evaporated, additional heptane (4 mL) was added. The suspension was filtered through a sintered funnel (porosity n ° 3) and washed with 3x 0.4 mL of heptane. After vacuum drying at room temperature, co-crystal Form IV of the present invention was obtained as a white solid (264 mg, 48%).

[0625] The co-crystal Form IV thus obtained showed Figure 7 and it also shows the X-ray diffraction pattern (XRPD) disclosed above 1 H NMR and DSC spectra.

[0626] 2.5. Cocrystal Form V

[0627] Preparation method of pulping from high-purity CBD

[0628] To a cylindrical vial equipped with magnetic stirring and N2 atmosphere containing a mixture of CBD (399 mg, 1.269 mmol, 2 eq.) and DL-proline (74 mg, 0.643 mmol) was added heptane (4 mL). The resulting mixture was stirred at room temperature overnight. Then, additional heptane (3 mL) was added because the solvent was partially evaporated. The suspension was filtered through a sintered funnel (porosity n°3) and washed with 3x 0.4 mL of heptane. After vacuum drying at room temperature, co-crystal Form V of the present invention was obtained as a white solid (252 mg, 46%).

[0629] The co-crystal Form V thus obtained exhibited Fig. 9 and it also shows the X-ray diffraction pattern (XRPD) disclosed above 1 H NMR and DSC spectra.

[0630] 2.6. Cocrystal Form VI

[0631] Preparation method of pulping from high-purity CBD

[0632] Heptane (0.55 mL) was added to a test tube equipped with magnetic stirring and containing a mixture of CBD (79 mg, 0.251 mmol, 3 eq.) and (2S, 3aS, 7aS)-octahydro-1H-indole-2-carboxylic acid (14 mg, 0.084 mmol). The resulting mixture was stirred overnight at room temperature. The suspension was filtered through a sintered funnel (porosity n° 3) and washed with 3 x 0.08 mL of heptane. After vacuum drying at room temperature, co-crystal Form VI of the present invention (possibly contaminated with (2S, 3aS, 7aS)-octahydro-1H-indole-2-carboxylic acid) was obtained as a white solid (25.2 mg, 48%).

[0633] The co-crystal Form VI thus obtained showed Fig.12 X-ray diffraction pattern (XRPD) in Fig.13 The co-crystal Form VI thus obtained also showed the above disclosed 1 H NMR.

[0634] 2.7. Cocrystal Form VII

[0635] Preparation Method A

[0636] In a test tube equipped with a magnetic stirrer, THC (23.7 mg, 0.08 mmol, 94% a / a by GC, obtained in Comparative Example 4.2a below), L-proline (9.3 mg, 0.08 mmol, 1 eq.) and heptane (0.25 mL, 10 V) were added. The suspension was stirred at room temperature overnight to obtain a concentrated suspension. Heptane (0.25 mL, 10 V) was added and stirred for 4 hours. The suspension was centrifuged, decanted and dried under vacuum (about 1 mbar, room temperature) overnight to obtain the co-crystal Form VII of the present invention mixed with L-proline as a white solid.

[0637] Preparation method B

[0638] In a 25 mL round bottom flask equipped with a magnetic stirrer and N2 atmosphere, THC (1.00 g, 3.18 mmol, 95% a / a by GC, obtained in Comparative Example 4.2b below), L-proline (219.7 mg, 1.91 mmol, 0.6 eq.) and heptane (10 mL, 10 V) were added. The suspension was stirred at room temperature for 2 days to obtain a concentrated suspension. Heptane (2 mL, 2 V) was added and stirred for 1 hour. The suspension was filtered through a sintered funnel (porosity n°3) and washed with heptane (2 x 2 mL, 2 x 2 V) and dried under vacuum (about 1 mbar, room temperature) overnight to obtain the co-crystal form VIII of the present invention as a white solid (704 mg, 86% yield).

[0639] The co-crystal Form VII thus obtained showed Fig.14 X-ray diffraction pattern (XRPD) in Fig.15 The co-crystal Form VII thus obtained also showed the above disclosed 1 H NMR.

[0640] 2.8. Cocrystal Form VIII

[0641] Preparation Method A

[0642] In a test tube equipped with a magnetic stirrer, THC (24.3 mg, 0.08 mmol, 94% a / a by GC, obtained in Comparative Example 4.2a below), D-proline (9.7 mg, 0.08 mmol, 1 eq.) and heptane (0.38 mL, 15 V) were added. The suspension was stirred at room temperature for 3 hours to obtain a concentrated suspension. Heptane (0.12 mL, 5 V) was added and stirred overnight at room temperature. The suspension was filtered through a sinter funnel (porosity 3) and washed with heptane (0.12 mL, 5 V) and dried under vacuum (about 1 mbar, room temperature) overnight to obtain the co-crystal Form VIII of the present invention mixed with D-proline as a white solid.

[0643] Preparation method B

[0644] In a 25 mL round bottom flask equipped with a magnetic stirrer and N2 atmosphere, THC (1.00 g, 3.18 mmol, 95% a / a by GC, obtained in Comparative Example 4.2b below), D-proline (219.7 mg, 1.91 mmol, 0.6 eq) and heptane (10 mL, 10 V) were added. The suspension was stirred at room temperature for 2 days and filtered through a sintered funnel (porosity 3), washed with heptane (2 x 2 mL, 2 x 2 V) and dried under vacuum (about 1 mbar at room temperature) overnight to obtain the co-crystal form VIII of the present invention as a white solid (782 mg, 96% yield).

[0645] The co-crystal Form VIII thus obtained showed Fig.16 X-ray diffraction pattern (XRPD) in Fig.17 The co-crystal form VIII thus obtained also showed the above disclosed 1 H NMR.

[0646] 2.9. Cocrystal Form IX

[0647] Preparation of Δ8-tetrahydrocannabinol

[0648] After column chromatography purification of the crude product obtained from CBD, Δ8-tetrahydrocannabinol (Δ8-THC) was obtained with a purity of about 97.2% a / a as measured by HPLC (Method 1).

[0649] Method for preparing co-crystals

[0650] In a test tube equipped with a magnetic stirrer, Δ8-THC (24.7 mg, 0.08 mmol), L-proline (5.5 mg, 0.05 mmol, 0.6 eq) and heptane (0.25 mL, 10 V) were added. The suspension was stirred at room temperature for 3 hours to obtain a thick suspension. Heptane (0.25 mL, 10 V) was added and stirred overnight. The suspension was filtered and dried under vacuum (about 1 mbar at room temperature) for 4 hours. The co-crystal Form IX of the present invention was obtained as a white solid.

[0651] The co-crystal Form IX thus obtained showed Fig.18 X-ray diffraction pattern (XRPD) in HPLC analysis indicated significant purification of Δ8-THC (about 99.4% a / a HPLC—method 1).

[0652] 2.10. Cocrystal Form X

[0653] Preparation of Δ8-THC

[0654] After column chromatography purification of the crude product obtained from CBD, a crude product of Δ8-tetrahydrocannabinol (Δ8-THC) was obtained with a purity of about 97.2% a / a as measured by HPLC (Method 1).

[0655] Method for preparing co-crystals

[0656] In a test tube equipped with a magnetic stirrer, Δ8-THC (26.2 mg, 0.08 mmol), D-proline (6.2 mg, 0.08 mmol, 0.6 eq.) and heptane (0.25 mL, 10 V) were added. The suspension was stirred at room temperature overnight. The white suspension was filtered through a sinter funnel (porosity 4), washed with heptane (0.1 mL, 4 V) and dried under vacuum (about 1 mbar at room temperature) for 3 hours. The co-crystal Form X of the present invention was obtained as a white solid.

[0657] The co-crystal Form X thus obtained exhibits Fig.19 X-ray diffraction pattern (XRPD) in.

[0658] 2.11. Cocrystal Form XI

[0659] Preparation of CBN

[0660] CBN used for co-crystal screening was directly prepared from CBD by reaction with iodine in toluene at 110°C (following the method disclosed in J. Nat. Prod. 2018, vol. 81(3), pp. 630-633). Crude CBN (about 81% a / a HPLC) and CBN purified by chromatography column (about 95-97% a / a HPLC) were used as starting materials.

[0661] Method for preparing co-crystals

[0662] Method 1: In an Eppendorf tube equipped with a magnetic stir bar, CBN (30 mg, 0.097 mmol - 95% a / a HPLC), betaine hydrate (11.3 mg, 0.083 mmol, 0.85 eq.) and heptane (0.6 mL, 20 V) were added. The resulting solution was stirred overnight at room temperature. The precipitated solid was centrifuged, the supernatant was decanted, and the solid was dried under vacuum (about 1-2 mbar, RT) overnight. According to XRPD, Form XI of the present invention was obtained as a mixture with betaine hydrate.

[0663] Method 2:In a flask equipped with a magnetic stir bar, CBN (130 mg, 0.418 mmol - 81% a / a HPLC), betaine hydrate (28.2 mg, 0.195 mmol, 0.5 eq.) and heptane (2.3 mL, 17 V) were added. The resulting suspension was stirred overnight at room temperature. The solid was filtered through a sintered funnel (porosity 3), washed with heptane (2x0.2 mL) and dried under vacuum (about 1 mbar, RT) overnight. Form XI of the present invention was obtained in a 1: 1 molar ratio (CBN: betaine) as an off-white solid (70.3 mg, 40% yield).

[0664] The co-crystal Form XI thus obtained showed Fig. 20 X-ray diffraction pattern (XRPD) in.

[0665] 2.12. Cocrystal Form XII

[0666] The preparation of CBN was carried out according to the method disclosed above for co-crystal Form XI.

[0667] Method for preparing co-crystals

[0668] Method 1: CBN (30 mg, 0.097 mmol - 95% a / a HPLC), L-proline (11.1 mg, 0.097 mmol, 1 eq.) and heptane (0.6 mL, 20 V) were added to an Eppendorf tube equipped with a magnetic stir bar. The resulting solution was stirred overnight at room temperature. The precipitated solid was centrifuged, the supernatant was decanted and the solid was dried under vacuum (about 1-2 mbar, RT) overnight. According to XRPD, Form XII of the invention was obtained as a mixture with L-proline as an off-white solid.

[0669] Method 2: In a flask equipped with a magnetic stir bar, CBN (200 mg, 0.644 mmol - 97% a / a HPLC), L-proline (18.5 mg, 0.161 mmol, 0.25 eq.) and heptane (2 mL, 10 V) were added. The resulting suspension was stirred overnight at room temperature. The solid was filtered through a sintered funnel (porosity 3), washed with heptane (3 x 0.2 mL) and dried under vacuum (about 1 mbar, RT) overnight. Form XII of the invention was obtained in a 1: 1 molar ratio (CBN: L-proline) as an off-white solid (44 mg, 16% yield).

[0670] The co-crystal Form XII thus obtained showed Fig. 22 X-ray diffraction pattern (XRPD) in.

[0671] 2.13. Cocrystal Form XIII

[0672] The preparation of CBN was carried out according to the method disclosed above for co-crystal Form XI.

[0673] Method for preparing co-crystals

[0674] In a flask equipped with a magnetic stir bar, CBN (150 mg, 0.483 mmol - 81% a / a HPLC), L-proline (28 mg, 0.242 mmol, 0.5 eq.) and heptane (2.5 mL, 17 V) were added. The resulting suspension was stirred overnight at room temperature. The solid was filtered through a sintered funnel (porosity 3), washed with heptane (2 x 0.3 mL) and dried under vacuum (about 1 mbar, RT) overnight. Form XIII of the invention was obtained in a 1: 1 molar ratio (CBN: L-proline) as an off-white solid (87 mg, 40% yield).

[0675] The co-crystal Form XIII thus obtained showed Fig.24 X-ray diffraction pattern (XRPD) in.

[0676] 2.14. Cocrystal Form XIV

[0677] The preparation of CBN was carried out according to the method disclosed above for co-crystal Form XI.

[0678] Preparation method of co-crystal

[0679] In a flask equipped with a magnetic stir bar, CBN (180 mg, 0.580 mmol - 81% a / a HPLC), D-proline (26 mg, 0.230 mmol, 0.4 eq.) and heptane (1.5 mL, 10 V) were added. The resulting suspension was stirred overnight at room temperature. The solid was filtered through a sintered funnel (porosity 3), washed with heptane (2x0.3 mL) and dried under vacuum (about 1 mbar, RT) overnight. Form XIV of the invention was obtained in a 1: 1 molar ratio (CBN: D-proline) as an off-white solid (85 mg, 40% yield).

[0680] The co-crystal Form XIV thus obtained exhibited Fig.26 X-ray diffraction pattern (XRPD) in.

[0681] 2.15. Cocrystal Form XV

[0682] The preparation of CBN was carried out according to the method disclosed above for co-crystal Form XI.

[0683] Method for preparing co-crystals

[0684] Method 1: In a flask equipped with a magnetic stir bar, CBN (100 mg, 0.322 mmol - 97% a / a HPLC), D-proline (18 mg, 0.161 mmol, 0.5 eq.) and heptane (2 mL, 20 V) were added. The resulting suspension was stirred overnight at room temperature. The solid was filtered through a sintered funnel (porosity 3), washed with heptane (2 x 0.2 mL) and dried under vacuum (about 1 mbar, RT) overnight. Form XV of the invention was obtained in a 1: 1 molar ratio (CBN: D-proline) as an off-white solid (41 mg, 30% yield).

[0685] The co-crystal Form XV thus obtained exhibits Fig.28 X-ray diffraction pattern (XRPD) in.

[0686] 2.16. Cocrystal Form XVI

[0687] Preparation of CBG

[0688] As disclosed in the prior art (US2017283837, WO2014134281, WO2016 / 30828, US2017 / 298399, US2017362195, Tet. Lett. 1969, 5349, Proceedings of Chemical Society 1964, 82, The Journal of Biological Chemistry 1996, 271(21), 17411), the CBG used is directly prepared by reaction between geraniol (1) and olive phenol (2) in chloroform in the presence of PTSA (0.04 eq.) at room temperature. After 18 hours, CBG is recovered as a mixture with about 20% regio-CBG and about 5-15% disubstituted CBG:

[0689]

[0690] Purification by column chromatography (x2) provided pure CBG (99.7% a / a HPLC - about 19% yield).

[0691] Method for preparing co-crystals

[0692] The pure form of CBG was obtained by evaporation from the mixture (10 V, 1:1 molar ratio, CBG:betaine) in heptane with 5% v / v EtOH. Cocrystal Form XVI

[0693] The contamination of other crystalline forms was obtained by the following method Cocrystal Form XVI :

[0694] - Evaporation from a mixture in heptane (10 V, 1:1 molar ratio, CBG:betaine) (contaminated with other forms and betaine)

[0695]

[0696] - Slurried in heptane with 5% v / v EtOH at 0-5°C (10V, 1:1 molar ratio, CBG:betaine) (contaminated with betaine)

[0697] Method 1: In a test tube equipped with a magnetic stirrer, CBG (20 mg, 0.063 mmol), betaine (7.8 mg, 0.067 mmol, 1 eq) and heptane (0.2 mL, 10 V) with 5% v / v EtOH were added. The suspension was stirred at room temperature but quickly turned into a paste. The mixture was concentrated to dryness and dried in vacuo (about 1 mbar, RT) overnight. Co-crystal Form XVI of the present invention was obtained as a white solid.

[0698] The co-crystal Form XVI thus obtained exhibited Fig.30 X-ray diffraction pattern (XRPD) in.

[0699] 2.17 Cocrystal Form XVII

[0700] Preparation of CBG The procedure disclosed above for co-crystal Form XVI was followed.

[0701] Method for preparing co-crystals

[0702] Co-crystal Form XVII was obtained:

[0703] - By slurrying in heptane (10V, 1:1 molar ratio, CBG:L-carnitine), a mixture with its crystalline form was obtained. However, upon exposure of the recovered solid to ambient conditions, pure Form XVII was recovered.

[0704] -The pure state is obtained by the following method:

[0705] Slurry in toluene (10V, 1:1 molar ratio, CBG:L-carnitine) (obtained as a gel)

[0706] Slurry in heptane with 5% EtOH (10V, 1:1 molar ratio, CBG:L-carnitine) (obtained as a paste)

[0707] Method 1: In a test tube equipped with a magnetic stirrer, CBG (50 mg, 0.16 mmol), L-carnitine (26 mg, 0.16 mmol, 1 eq.) and heptane (0.5 mL, 10 V) were added. The resulting suspension was stirred overnight at room temperature. The solid was filtered through a sintered funnel (porosity 3), washed with heptane (0.1 mL, 2 V) and dried under vacuum (about 1 mbar, RT) overnight. A mixture of co-crystal Form XVII and other co-crystal forms (57 mg) was obtained, which was converted to co-crystal Form XVII of the present invention (1:1 molar ratio, CBG:L-carnitine, according to 1 H-NMR).

[0708] The co-crystal Form XVII thus obtained showed Fig.33 X-ray diffraction pattern (XRPD) in.

[0709] 2.18 Cocrystal Form XVIII

[0710] Preparation of CBDV

[0711] The CBDV used as the starting material in the present invention was prepared in a similar manner to that used to prepare synthetic CBD ( 5-propylresorcinol was used as starting material instead of olivetol). After crystallization from the crude product, CBDV was obtained with a purity of about 96% a / a according to HPLC.

[0712] Method for preparing co-crystals

[0713] Co-crystal Form XVIII was obtained as pure form by slurrying in iBuOH (4V, 3:2 molar ratio, CBDV:L-proline).

[0714] Method 1: In a test tube equipped with a magnetic stirrer, CBDV (50 mg, 0.175 mmol), L-proline (10 mg, 0.087 mmol, 2 eq.) and isobutanol (0.25 mL, 5 V) were added. The resulting solution was stirred at room temperature for 1 week. The precipitated solid was centrifuged, the supernatant was decanted, and the solid was dried under vacuum (about 1-2 mbar, RT) overnight. The co-crystal form XVIII of the present invention was obtained as an off-white solid.

[0715] Method 2: In a test tube equipped with a magnetic stirrer, CBDV (100 mg, 0.349 mmol), L-proline (27 mg, 0.233 mmol, 1.5 eq.) and isobutanol (0.4 mL, 4 V) were added. The resulting suspension was stirred overnight at room temperature. The solid was filtered through a sintered funnel (porosity 3), washed with heptane (2x0.15 mL, 2x1.5 V) and dried under vacuum (about 1 mbar, RT) overnight. Co-crystal Form XVIII of the present invention in a 1:1 molar ratio (CBDV:L-proline) was obtained as an off-white solid (51 mg, 27% yield).

[0716] The co-crystal Form XVIII thus obtained exhibited Fig.34 X-ray diffraction pattern (XRPD) in.

[0717] 2.19 Cocrystal Form XIX

[0718] Preparation of CBDV The procedure disclosed above for co-crystal Form XIX was followed.

[0719] Method for preparing co-crystals

[0720] Co-crystal Form XIX was obtained in pure form by slurrying in IPA (2V, 2:3 molar ratio, CBDV:L-carnitine).

[0721] Method 1: To a 2 mL Eppendorf tube containing CBDV (20 mg, 0.070 mmol), L-carnitine (11 mg, 0.070 mmol, 1 eq.) and three stainless steel grinding balls, 2 drops of IPA were added. The product was ground for 45 minutes at a rate of 30 Hz (3 cycles of 15 minutes) using a Retsch ball mill MM 400. After vacuum drying (about 1-2 mbar, RT) overnight, the co-crystal Form XIX of the present invention contaminated with CBDV was obtained as a white solid.

[0722] Method 2: In a test tube equipped with a magnetic stirrer, CBDV (100 mg, 0.349 mmol), L-carnitine (84 mg, 0.524 mmol, 1.5 eq.) and IPA (0.2 mL, 2 V) were added. The resulting suspension was stirred overnight at room temperature. The solid was filtered through a sintered funnel (porosity 3), washed with IPA (2x0.1 mL, 2x1 V) and dried under vacuum (about 1 mbar, RT) overnight. Form XIX of the present invention was obtained in a 1:1 molar ratio (CBDV:L-carnitine) as an off-white solid (104 mg, 66% yield).

[0723] The co-crystal Form XIX thus obtained exhibited Fig.36 X-ray diffraction pattern (XRPD) in.

[0724] 3. Stability study

[0725] 3.1.CBD

[0726] The aim of the study was to evaluate the stability of co-crystal Form I of the present invention.

[0727] sample

[0728] The co-crystal Form I of the present invention is obtained by the method disclosed in Section 2.1.B.1.

[0729] method

[0730] Cocrystal Form I (55 mg) was stored in an open vial and exposed to accelerated stability conditions (40°C and 75±5% relative humidity) according to the ICH guidelines (Guidance for Industry Q1A(R2) Stability Testing of New Drug Substances and Products - available at http: / / www.ich.org / products / guidelines / quality / quality-single / article / stability-testing-of-new-drug-substances-and-products.html on August 4th, 2017).

[0731] result

[0732] Under the above conditions, co-crystal Form I of the present invention remains stable for at least three weeks according to XRPD.

[0733] 3.2.THC

[0734] The study aims to evaluate the stability of cocrystal form VIII

[0735] sample

[0736] The co-crystal Form VIII of the present invention is obtained by the method disclosed in Section 2.8.

[0737] method

[0738] Co-crystal Form VIII and oily THC were exposed to two different stability conditions:

[0739] - Condition 1: Co-crystal Form VIII (700 mg - 96.5% a / a HPLC - Method 2) and THC (700 mg - 94.8% HPLC - Method 2): Open vial at ambient conditions (21 ± 4 °C and 43 ± 13% relative humidity, exposed to laboratory light)

[0740] - Condition 2: Co-crystal Form VIII (100 mg - 95.9% a / a HPLC - Method 2) and THC (100 mg - 95.6% HPLC - Method 2): Closed vials stored at 40 ± 2 °C

[0741] result

[0742] Based on HPLC (Method 2), it was observed that co-crystal Form VIII maintained a higher chemical stability than oily THC:

[0743] -Chemical purity after 14 weeks under condition 1:

[0744] 88.9% a / a co-crystal Form VIII and 83.7% a / a oily THC

[0745] -Chemical purity after 10 weeks under condition 2:

[0746] 89.1% a / a co-crystal Form VIII and 76.6% a / a oily THC

[0747] also, According to XRPD, co-crystal Form VIII of the present invention remains stable.

[0748] 4. Purification studies

[0749] 4.1.CBD

[0750] The aim of this study was to measure the purity of the CBD co-crystals of the invention and compare it with the purity of CBD samples used as starting material and CBD purified by co-crystallization of co-crystal Form I.

[0751] Samples

[0752] Sample 1: Commercial hemp flower extract containing 50 wt% CBD relative to the total weight of the extract.

[0753] Sample 2: Pure commercial CBD used as starting material in the preparation of CBD co-crystals.

[0754] Sample 3: Pure CBD obtained from cannabis flower extract after purification via co-crystallization of Form I and subsequent co-crystal dissociation step.

[0755] method

[0756] Each sample (5 mg) was dissolved in methanol (5 mL) and injected (1 μL) for HPLC measurement under isocratic conditions (acetonitrile:water 80:20) with a detector at 225 nm (HPLC method 1).

[0757] result

[0758] The purity and impurity profile of the CBD used as starting materials (samples 1 and 2) and the CBD obtained after purification of sample 1 (sample 3) are disclosed in Table 11A. The purity and impurity profile of co-crystal Form I and Form II of the present invention prepared from Sample 1 are disclosed in Table 11B.

[0759] The purity of the starting material, the co-crystals of the invention and the CBD obtained after dissociation of the co-crystals of the invention as well as the amount of impurities are expressed in area %.

[0760] Table 11A

[0761]

[0762] (1) Most impurities were not detected by HPLC.

[0763] (2) The CBD C4 analog corresponds to 2-[(1R,6R)-6-isopropenyl-3-methylcyclohex-2-en-1-yl]-5-butylbenzene-1,3-diol.

[0764] (3) THC corresponds to tetrahydrocannabinol.

[0765] (43) ND stands for not detected.

[0766] Table 11B

[0767]

[0768] (1) The CBD C4 analog corresponds to 2-[(1R,6R)-6-isopropenyl-3-methylcyclohex-2-en-1-yl]-5-butylbenzene-1,3-diol.

[0769] (2) THC corresponds to tetrahydrocannabinol.

[0770] (3) Under HPLC conditions, no L-proline was detected in co-crystal Form I.

[0771] (4) Under HPLC conditions, no betaine in co-crystal Form II was detected.

[0772] (5) ND stands for not detected.

[0773] As shown in the table above, the co-crystal preparation of the present invention allows purification of CBD, especially crude CBD, in a less labor-intensive, less expensive and more scalable process than the prior art. When the CBD used as the starting material has a purity of 50% w / w and even when the starting CBD already has a high purity (about 98 area %), the co-crystal preparation of the present invention still allows purification of CBD, especially co-crystal Form I, Form II and Form IV.

[0774] Form I obtained from Sample 1 was dissociated in a biphasic heptane / water mixture, resulting in a CBD (Sample 3) with a slightly higher purity (99.66% a / a) than Form I (99.26% a / a), significantly higher purity than Sample 1 (50% purity by weight, 98.00 a / a), and an overall yield of 35% (including co-crystallization and co-crystal dissociation steps, with a maximum of 50% yield). In addition, 1 H NMR analysis showed that UV-undetectable coformers and impurities were removed (see Figure 5 ), HPLC analysis showed that UV detectable impurities were also reduced. In fact, cannabidiol was reduced from 0.88% a / a to undetectable amounts and CBD C4 analogue was reduced from 0.28% to 0.16% a / a, and XRPD analysis showed that the crystalline form was identical to commercially pure CBD ( Figure 6 ).

[0775] Furthermore, the preparation of the co-crystal from the inventive sample 2 also allowed the reduction of the amount of all identified impurities. In particular, the amount of THC was reduced by half.

[0776] 4.2.THC

[0777] The aim of this study was to improve the purity of THC obtained by co-crystallization followed by dissociation of the co-crystals of the invention compared to THC obtained by chromatographic purification. It is worth noting that direct crystallization is not possible since THC does not crystallize.

[0778] Comparative Example 4.2a

[0779] According to the method disclosed in Example II on page 9 of PCT patent application WO02070506, crude THC with a purity of 77% a / a as measured by GC was obtained.

[0780] Chromatographic purification of the crude product gave THC with a purity of 94% a / a as measured by GC, in a yield of 49%. The chromatographic purification of the crude product was carried out using a 40 g SiO2-GOLD column and eluting the crude product with a mixture of cyclohexane / 20% Et2O-cyclohexane.

[0781] Example 4.2b

[0782] Step 1. Cocrystal formation

[0783] According to the method disclosed in Example II on page 9 of PCT patent application WO02070506, crude THC with a purity of 77% a / a as measured by GC was obtained.

[0784] In a 100 mL round bottom flask equipped with a magnetic stirrer, crude THC (4.60 g, 14.6 mmol), L-proline (1.68 g, 14.6 mmol, 1 eq) and heptane (46 mL, 10 V) were added. The suspension was stirred at room temperature for 2 days and filtered through a sintered funnel (porosity 3), washed with heptane (2 x 9 mL, 2 x 2 V) and dried under vacuum (about 1 mbar, room temperature) overnight to obtain co-crystal Form VII of the present invention mixed with L-proline as a white solid (4.66 g).

[0785] As shown in Examples 4.2a and 4.2b, the purification process of the invention involving co-crystallization of THC allows THC to be obtained in high purity (equal to or higher than 95% a / a measured by GC) and in high yield (equal to or higher than 65%).

[0786] Step 2. Dissociation process

[0787] In a 1 L round bottom flask equipped with a magnetic stirrer, the co-crystal Form VII and L-proline mixture from step 1 (4.50 g) was dissolved in H2O (180 mL, 40 V) and heptane (360 mL, 80 V). The suspension was stirred at room temperature for 10 minutes and decanted. The aqueous phase was extracted with heptane (3 x 90 mL, 3 x 15 V). The organic phase (optionally dried over Na2SO4) was concentrated to dryness to give THC as a light brown oil (2.80 g, 63% total chlorine production - 2 steps) with a purity of 95% a / a by GC.

[0788] As shown above, the co-crystal preparation of the present invention allows for a less labor intensive, less expensive and more scalable process for purifying THC, especially crude THC, compared to the prior art.

[0789] 4.3.CBN

[0790] The aim of this study was to observe the improvement in the purity of CBN obtained by co-crystallization followed by dissociation of the co-crystals of the invention compared to the purity of CBN obtained from chromatographic purification. Although the crystalline form of CBN is described in the literature, it was not obtainable during this study even from very pure CBN material. Therefore, it was not possible to compare the co-crystallization of CBN with direct crystallization.

[0791] Step 1. Cocrystal formation

[0792] CBN (1 g, 80.8%) was dissolved in 20V heptane and betaine hydrate (377 mg, 2.79 mmol, 0.85 eq.) was added to the solution to obtain a suspension. Inoculation with form XI (obtained in method 2 of example 2.11) was performed. The resulting mixture was stirred at room temperature overnight. The solid was isolated by filtration and washed with heptane (2x 2V) and then dried under vacuum at room temperature overnight.

[0793] Co-crystal Form XI with residual betaine was obtained as a white solid (700 mg, 99.6% a / a by HPLC (Method 2).

[0794] Step 2. Dissociation process

[0795] The co-crystal form XI (700 mg) with residual betaine obtained in the previous step was dissolved in a 120V heptane:water mixture (2: 1) and 4V HCl 1M. After separation of the organic phase, the aqueous phase was extracted with heptane (3x 20V). The combined organic phase was then washed with water (3 times) until a neutral pH was reached. The organic phase was subsequently dried over anhydrous MgSO4, and decompressed and evaporated in vacuo to dryness. CBN was obtained as a colorless oil (344 mg, 99.6% a / a measured by HPLC (method 2), with an overall yield of 43% (two steps)).

[0796] As shown above, the co-crystal preparation of the present invention allows for a less labor intensive, less expensive and more easily scalable process to purify CBN, especially crude CBN, compared to the prior art.

[0797] 4.4.CBDV

[0798] The aim of this study was to measure the purity of CBDV obtained by co-crystals of the invention which were co-crystallized and then dissociated, compared to the purity of CBDV produced from direct crystallization.

[0799] Step 1. Cocrystal formation

[0800] Co-crystal Form XIX was prepared by slurrying the crude CBDV product from the synthesis (with a purification step).

[0801] In a test tube equipped with a magnetic stirrer, CBDV (300 mg, 1.047 mmol), L-carnitine (338 mg, 2.095 mmol, 2 eq.) and IPA (0.6 mL, 2 V) were added. A thick suspension was obtained and IPA (0.3 mL, 1 V) was added. The resulting suspension was stirred at room temperature overnight. The mixture was filtered through a sintered funnel (porosity 3), washed with IPA (2x0.3 mL, 2x1 V) and vacuum dried (about 1 mbar, RT) overnight. Co-crystal Form XIX of the present invention in a 1: 1 molar ratio (CBDV: L-carnitine) was obtained as an off-white solid (424 mg, 91% yield).

[0802] Step 2. Dissociation process. Preparation of CBDV from co-crystal Form XIX

[0803] In a 50 mL round bottom flask equipped with a magnetic stirrer, the co-crystal Form XIX (300 mg) from step 1 was suspended in H2O (12 mL, 40 V) and toluene (12 mL, 40 V). The suspension was stirred at room temperature for 10 minutes and decanted. The aqueous phase was extracted with toluene (3 x 12 mL, 3 x 40 V). The combined organic extracts (optionally dried with Na2SO4) were concentrated to dryness to give an off-white solid (125 mg, 59% overall yield - 2 steps) with a purity of 98.8% a / a as measured by HPLC (Method 2).

[0804] Good purification results were also observed by direct crystallization of CBDV in heptane. 1 H NMR spectrum, the main impurity detected in the obtained CBDV (about 3% a / a measured by HPLC method 2) is a compound derived from the isopropyl impurity formed in the preparation of 1,3-dimethoxy-5-propylbenzene. However, it was checked that this impurity was not removed from further recrystallization in heptane, but could be easily removed by co-crystallization, resulting in higher purity.

[0805] Citation List

[0806] 1.T.Petrzilka et al. "synthese und des(-)-cannabidiols mitteilung". Helvetica Chimica Acta. 1967, Vol. 50(2), pp. 719-23

[0807] 2.T.Petrzilka et al. "synthese von haschisch-inhaltsstoffen.4.Mitteilung".Helvetica Chimica Acta.1969, Volume 52(4), Pages 1102-34

[0808] 3. WO2009018389

[0809] 4. Tetrahedron Letters 1985, Vol. 26(8), p. 1083

[0810] 5.WO2006133941

[0811] 6.WO2007041167

[0812] 7.WO2015032519

[0813] 8. Biochemical Medicine, 1973, Vol. 8(3), pp. 341-344

[0814] 9.WO2004026857A2-GW

[0815] 10. Preparative Biochemistry, 1973, Vol. 3(3), pp. 209-220

[0816] 11. Poster ACS, Philadelphia, 2016, Biotage

[0817] 12.US2017008870A1

[0818] 13.US4381399A

[0819] 14.US2018325861

[0820] 15. Indian J. Pharm. Sci. 2017, Vol. 79(6), pp. 858-871

[0821] 16.US2017283837

[0822] 17.WO2014134281

[0823] 18. WO2016 / 30828

[0824] 19.US2017 / 298399

[0825] 20.US2017362195

[0826] 21. Tet. Lett. 1969, 5349,

[0827] 22.Proceedings of Chemical Society 1964, 82,

[0828] 23.The Journal of Biological Chemistry 1996, 271(21), 17411

[0829] 24. British Journal of Pharmacology, 2018, 175 100–112

[0830] 25.Sci Rep, 2016, 6:29789,1-1526.Chem Commun, 1969, 7, 343–344

[0831] 27. Tetrahedron 2017, 73, 5297-5301

[0832] 28.J.Nat.Prod.2018, 81(3), 630-633

[0833] 29.Tet.Lett.1985, 26(8), 1083-1086

[0834] For reasons of completeness, various aspects of the invention are set out in the following numbered clauses:

[0835] Item 1. A solid composition comprising:

[0836] an effective amount of co-crystals of one or more cannabinoids and a zwitterionic coformer; and

[0837] one or more acceptable excipients or carriers;

[0838] The effective amount of the co-crystal is 1 to 80 wt % of the solid composition.

[0839] Clause 2. The solid composition according to Clause 1, wherein the effective amount of the co-crystal is 10 to 40% by weight of the solid composition.

[0840] Item 3. The solid composition according to any one of Items 1 or 2, wherein the particle size of the co-crystals is from 50 μm to 250 μm.

[0841] Clause 4. The solid composition according to any one of clauses 1 to 3, wherein the solid composition is a hard capsule, a direct compression tablet and a dry granulation tablet.

[0842] Clause 5. The solid composition according to clause 4, wherein the solid composition is:

[0843] Hard capsules, containing

[0844] 1 to 80% by weight of one or more cannabinoid co-crystals;

[0845] 20 to 99 weight percent of one or more fillers; and

[0846] 0.25 to 10% by weight of one or more glidants;

[0847] The sum of the components of the composition is 100% by weight;

[0848] or,

[0849] Dry granulated tablets, containing:

[0850] 1 to 80% by weight of one or more cannabinoid co-crystals;

[0851] 20 to 99 weight percent of one or more fillers;

[0852] 1 to 15% by weight of one or more disintegrants;

[0853] 0.25 to 10% by weight of one or more glidants; and

[0854] 0.25 to 10 wt. % of one or more lubricants;

[0855] The sum of the components of the composition is 100% by weight;

[0856] or,

[0857] Direct compression tablets: Contains:

[0858] 1 to 80% by weight of one or more cannabinoid co-crystals;

[0859] 20 to 99 weight percent of one or more fillers; and

[0860] 0.25 to 10% by weight of one or more glidants;

[0861] The sum of the components of the composition is 100% by weight.

[0862] Clause 6. A solid composition according to any one of clauses 1 to 5, wherein the cannabinoid is selected from the group consisting of tetrahydrocannabinol, cannabidiol, cannabinol, cannabigerol, cannachromene, cannabicyclol, cannabinol, tetrahydrocannabinol, cannabidiol, cannachromene, cannabigerol, cannabigerol monomethyl ether, Δ8-tetrahydrocannabinol and mixtures thereof.

[0863] Clause 7. The solid composition of any one of Clauses 1-6, wherein the coformer comprises a positively charged nitrogen atom and a negatively charged group distal to the positively charged nitrogen group on the zwitterion, separated by at least one carbon atom.

[0864] Clause 8. The solid composition of any one of Clauses 1-7, wherein the coformer is selected from the group consisting of L-proline, betaine, L-carnitine, D-proline and DL-proline.

[0865] Clause 9. The solid composition according to clause 8, wherein the eutectic of the solid composition is selected from the group consisting of

[0866] 2-[(1R,6R)-6-isopropenyl-3-methylcyclohex-2-en-1-yl]-5-pentylbenzene-1,3-diphenol and L-proline, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.8, 11.1, and 15.8 ± 0.3 degrees 2θ;

[0867] 2-[(1R,6R)-6-isopropenyl-3-methylcyclohex-2-en-1-yl]-5-pentylbenzene-1,3-diphenol and betaine, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 9.1, 10.7, and 18.4 ± 0.3 degrees 2θ;

[0868] 2-[(1R,6R)-6-isopropenyl-3-methylcyclohex-2-en-1-yl]-5-pentylbenzene-1,3-diphenol and L-carnitine, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 6.8, 11.3, and 20.0 ± 0.3 degrees 2θ;

[0869] 2-[(1R,6R)-6-isopropenyl-3-methylcyclohex-2-en-1-yl]-5-pentylbenzene-1,3-diphenol and D-proline, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.7, 11.2, and 15.7 ± 0.3 degrees 2θ;

[0870] 2-[(1R,6R)-6-isopropenyl-3-methylcyclohex-2-en-1-yl]-5-pentylbenzene-1,3-diphenol and DL-proline, characterized in that Cu-K αIts X-ray diffraction pattern under radiation contains characteristic peaks at 5.7, 11.1, and 15.7 ± 0.3 degrees 2θ;

[0871] (-)-(6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,8,10a-tetrahydro-6H-benzo[c]chromen-1-ol and L-proline, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.1, 11.5, and 20.5 ± 0.3 degrees 2θ;

[0872] (-)-(6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,8,10a-tetrahydro-6H-benzo[c]chromen-1-ol and D-proline, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.1, 11.4, and 20.6 ± 0.3 degrees 2θ;

[0873] (6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,10,10a-tetrahydro-6H-benzo[c]chromene-1-ol and L-proline, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.1, 18.7 and 20.5 ± 0.3 degrees 2θ; and

[0874] (6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,10,10a-tetrahydro-6H-benzo[c]chromene-1-ol and L-proline, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.1, 16.1 and 20.4 ± 0.3 degrees 2θ.

[0875] Item 10. A co-crystal of a cannabinoid selected from (-)-(6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,8,10a-tetrahydro-6H-benzo[c]chromen-1-ol and (6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,10,10a-tetrahydro-6H-benzo[c]chromen-1-ol and a zwitterionic coformer.

[0876] Clause 11. The co-crystal of Clause 10, wherein the coformer is selected from the group consisting of L-proline, D-proline and DL-proline.

[0877] Clause 12. The co-crystal according to any one of clauses 10 or 11, which is a co-crystal selected from the group consisting of:

[0878] (-)-(6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,8,10a-tetrahydro-6H-benzo[c]chromen-1-ol and L-proline, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.1, 11.5, and 20.5 ± 0.3 degrees 2θ;

[0879] (-)-(6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,8,10a-tetrahydro-6H-benzo[c]chromen-1-ol and D-proline, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.1, 11.4, and 20.6 ± 0.3 degrees 2θ;

[0880] (6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,10,10a-tetrahydro-6H-benzo[c]chromene-1-ol and L-proline, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.1, 18.7 and 20.5 ± 0.3 degrees 2θ; and

[0881] (6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,10,10a-tetrahydro-6H-benzo[c]chromene-1-ol and L-proline, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.1, 16.1 and 20.4 ± 0.3 degrees 2θ.

[0882] Clause 13. A method for preparing a co-crystal as defined in any one of clauses 10 to 12, the method comprising:

[0883] (c) slurrying the cannabinoid with the coformer and an organic solvent; and

[0884] (d) isolating the co-crystal thus obtained.

[0885] Clause 14. A method of purifying a cannabinoid, the method comprising:

[0886] (e) dissociating the co-crystal as defined in any one of clauses 10 to 12 under such reaction conditions to obtain the cannabinoid; and

[0887] (f) isolating the cannabinoids thus obtained.

Claims

1. A solid composition comprising: an effective amount of co-crystals of one or more cannabinoids and a zwitterionic coformer selected from the group consisting of L-proline and D-proline; and one or more acceptable excipients or carriers; wherein the effective amount of the co-crystal is 1 to 80 weight % of the solid composition; and The co-crystals of the solid composition are selected from the group consisting of: (-)-(6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,8,10a-tetrahydro-6H-benzo[c]chromene-1-ol and L-proline, characterized in that exist Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.1, 11.5, and 20.5 ± 0.3 degrees 2θ; (-)-(6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,8,10a-tetrahydro-6H-benzo[c]chromen-1-ol and D-proline, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.1, 11.4, and 20.6 ± 0.3 degrees 2θ; (6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,10,10a-tetrahydro-6H-benzo[c]chromene-1-ol and L-proline, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.1, 18.7, and 20.5 ± 0.3 degrees 2θ; (6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,10,10a-tetrahydro-6H-benzo[c]chromene-1-ol and D-proline, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.1, 16.1 and 20.4 ± 0.3 degrees 2θ.

2. The solid composition according to claim 1, wherein the effective amount of the co-crystal is 10 to 40% by weight of the solid composition.

3. The solid composition according to claim 1, wherein the particle size of the co-crystal is 50 μm to 250 μm.

4. The solid composition according to claim 1, wherein the solid composition is a hard capsule, a direct compression tablet and a dry granulation tablet.

5. The solid composition according to claim 4, wherein the solid composition is: Hard capsules, containing 1% to 80% by weight of one or more cannabinoid co-crystals; 20 to 99 wt % of one or more fillers; and 0.25% to 10% by weight of one or more glidants; The sum of the components of the composition is 100% by weight; or, Dry granulated tablets, containing: 1% to 80% by weight of one or more cannabinoid co-crystals; 20 to 99 wt % of one or more fillers; 1 to 15 wt % of one or more disintegrants; 0.25% to 10% by weight of one or more glidants; and 0.25 wt % to 10 wt % of one or more lubricants; The sum of the components of the composition is 100% by weight; or, Direct compression tablets: Contains: 1% to 80% by weight of one or more cannabinoid co-crystals; 20 to 99 wt % of one or more fillers; and 0.25% to 10% by weight of one or more glidants; The sum of the components of the composition is 100% by weight.

6. A co-crystal of a cannabinoid selected from (-)-(6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,8,10a-tetrahydro-6H-benzo[c]chromen-1-ol and (6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,10,10a-tetrahydro-6H-benzo[c]chromen-1-ol and a zwitterionic coformer selected from L-proline and D-proline, wherein the co-crystal is selected from the group consisting of: (-)-(6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,8,10a-tetrahydro-6H-benzo[c]chromene-1-ol and L-proline, characterized in that exist Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.1, 11.5, and 20.5 ± 0.3 degrees 2θ; (-)-(6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,8,10a-tetrahydro-6H-benzo[c]chromen-1-ol and D-proline, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.1, 11.4, and 20.6 ± 0.3 degrees 2θ; (6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,10,10a-tetrahydro-6H-benzo[c]chromene-1-ol and L-proline, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.1, 18.7, and 20.5 ± 0.3 degrees 2θ; (6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,10,10a-tetrahydro-6H-benzo[c]chromene-1-ol and D-proline, characterized in that Cu-K α Its X-ray diffraction pattern under radiation contains characteristic peaks at 5.1, 16.1 and 20.4 ± 0.3 degrees 2θ.

7. A method for preparing a co-crystal according to claim 6, the method comprising: (c) slurrying the cannabinoid with the coformer and an organic solvent; and (d) isolating the co-crystals thus obtained; wherein the zwitterionic coformer is selected from the group consisting of L-proline and D-proline; and The organic solvent in step (c) is selected from the group consisting of cyclo(C5-C7)alkanes, (C5-C9)alkanes and mixtures thereof.

8. The method for preparing a co-crystal according to claim 7, wherein the organic solvent in step (c) is heptane.

9. A method for purifying a cannabinoid selected from the group consisting of (-)-(6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,8,10a-tetrahydro-6H-benzo[c]chromen-1-ol and (6aR,10aR)-6,6,9-trimethyl-3-pentyl-6a,7,10,10a-tetrahydro-6H-benzo[c]chromen-1-ol, the method comprising: (e) dissociating the co-crystals as defined in claim 6 under reaction conditions to obtain the cannabinoid, comprising dissociating the co-crystals in an organic solvent, or in a mixture of water and one or more water-immiscible organic solvents, followed by separation of the phases of the two-phase mixture to obtain the cannabinoid, wherein the organic solvent is selected from the group consisting of (C1-C4)alkyl-CO-O-(C1-C4)alkyl, (C1-C4)alkyl-O-(C1-C4)alkyl, (C1-C4)alkyl-CO-(C1-C4)alkyl and (C1-C9)alkane, and the water-immiscible organic solvent is selected from the group consisting of (C5-C9)alkane, (C1-C4)alkyl-O-(C1-C4)alkyl and mixtures thereof; and (f) isolating the cannabinoids thus obtained.